Photosensitive resin composition set

JP2025023765APending Publication Date: 2025-02-17AJINOMOTO CO INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023128197
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-04
Publication Date
2025-02-17

Smart Images

  • Figure 2025023765000007
    Figure 2025023765000007
  • Figure 2025023765000008
    Figure 2025023765000008
  • Figure 2025023765000009
    Figure 2025023765000009
Patent Text Reader

Abstract

To provide a photosensitive resin composition set which enables manufacture of an optical waveguide that is excellent in developability and adhesion, is low in shrinkage, and is small in optical transmission loss.SOLUTION: There is provided a photosensitive resin composition set containing a resin composition for a core and a resin composition for a clad. At least the resin composition for the clad contains (A) a high molecular weight component having a glass transition temperature of 65°C or lower and a weight average molecular weight of 1,500 or more and less than 14,000. The resin composition for the core and the resin composition for the clad each contain (B) a resin containing a carboxyl group, (C) an epoxy resin, (D) a photocurable resin, and (E) a photopolymerization initiator. When Aclad represents a content (mass%) of the component (A) in the resin composition for the clad with a non-volatile component of the resin composition for the clad being 100 mass%, and Acore represents a content (mass%) of the component (A) in the resin composition for the core with a non-volatile component of the resin composition for the core being 100 mass%, there is satisfied a range of Aclad-Acore being 0.6 or more and 12 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a photosensitive resin composition set. The present invention further relates to a photosensitive resin sheet set, the photosensitive resin composition set, an optical waveguide, a method for producing an optical waveguide, an optical / electrical hybrid board, and a method for producing an optical / electrical hybrid board. [Background technology]

[0002] Technological advances such as 5G communications, autonomous driving, IoT, artificial intelligence, and big data have led to an increasing demand for ultra-high-speed and large-capacity communications. Semiconductor packages, which are the backbone of these communications, have traditionally supported high-speed communications by passing high-frequency currents through them. However, in recent years, issues of noise generation, communication loss, and heat generation due to high-speed communications have become evident. To solve these issues, active efforts have been made in recent years to implement optical circuits on electrical wiring boards and achieve energy savings, low latency, and high-speed communications (Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2019-211540 A [Patent Document 2] Patent No. 5771978 Summary of the Invention [Problem to be solved by the invention]

[0004] Especially in data centers where high-speed transmission is required, research into the introduction of silicon photonics is being actively conducted. Silicon photonics is highly compatible with conventional LSI manufacturing processes. Therefore, it is expected that the use of silicon photonics will enable the formation of nanometer-sized thin-wire waveguides at low cost based on the technology cultivated in electronic circuit integration technology.

[0005] For example, according to silicon photonics, it is expected that an optical integrated circuit will be formed on a chip using a fine-wire waveguide. When manufacturing an optoelectronic hybrid board equipped with this chip, it is required to provide an optical waveguide on the optoelectronic hybrid board in order to extract signal light from the fine-wire waveguide in the chip to the outside of the chip and connect it to wiring between chips. From the viewpoint of efficiently forming a fine optical waveguide, it is desirable to form the optical waveguide from a cured product of a photosensitive resin composition. In addition, since the optoelectronic hybrid board is required to have the same reliability as a printed circuit board, it is desirable that there is no significant change in optical transmission loss, and at the same time, it is desirable that the board has properties that can withstand the manufacturing process of the printed circuit board.

[0006] Furthermore, depending on the resin used between the core and the clad, the developability may decrease, and the difference in shrinkage rate between the core and the clad may change, resulting in an increase in optical transmission loss.

[0007] Furthermore, in recent years, it has been assumed that a conductor layer is provided by performing a metal plating process on the core layer of the optical waveguide. It is also desired to improve the adhesion between the core layer and the conductor layer. A method of roughening the surface of the core layer is considered to improve the adhesion between the core layer and the conductor layer, but roughening the surface of the core layer may increase the optical transmission loss of the optical waveguide due to the surface unevenness of the core layer caused by the roughening process.

[0008] The present invention has been devised in view of the above-mentioned problems, and aims to provide a photosensitive resin composition set capable of producing an optical waveguide having excellent developability and adhesion, a small difference in shrinkage rate, and small optical transmission loss; a photosensitive resin sheet set; an optical waveguide; a method for producing an optical waveguide; an optical-electrical hybrid board; and a method for producing an optical-electrical hybrid board. [Means for solving the problem]

[0009] As a result of intensive research, the inventors have found that the above-mentioned problems can be solved by combining and containing (A) a high molecular weight component having a glass transition temperature of 65° C. or less and a weight average molecular weight of 1,500 or more and less than 14,000, (B) a resin containing a carboxyl group, (C) an epoxy resin, (D) a photocurable resin, and (E) a photopolymerization initiator, and adjusting the content of component (E) in the core resin composition and the clad resin composition so that the content of component (E) satisfies a specific relationship, thereby completing the present invention.

[0010] That is, the present invention includes the following. [1] A photosensitive resin composition set including a core resin composition and a clad resin composition, At least the cladding resin composition is (A) a high molecular weight component having a glass transition temperature of 65° C. or lower and a weight average molecular weight of 1,500 or more and less than 14,000; Including, The core resin composition and the clad resin composition each comprise: (B) a resin containing a carboxyl group; (C) epoxy resin, (D) a photocurable resin, and (E) a photopolymerization initiator, The content (mass%) of component (A) in the clad resin composition is defined as A when the non-volatile components of the clad resin composition are defined as 100 mass%. clad The content (mass%) of component (A) in the core resin composition is defined as A when the non-volatile components of the core resin composition are defined as 100 mass%. core Then, A clad -A core A photosensitive resin composition set, which satisfies the range of 0.6 to 12. [2] The photosensitive resin composition set according to [1], wherein the content of component (A) is 0.1% by mass or more and 10% by mass or less, when the non-volatile components of the core resin composition are taken as 100% by mass. [3] The photosensitive resin composition set according to [1] or [2], wherein the content of component (A) is 0.1% by mass or more and 10% by mass or less, when the non-volatile components of the cladding resin composition are taken as 100% by mass. [4] The photosensitive resin composition set according to any one of [1] to [3], wherein the component (B) contains at least one of an aralkyl type resin, a naphthol aralkyl type resin, and a cardo type resin. [5] The content of component (B) when the non-volatile components of the core resin composition are 100% by mass is B core The content of component (C) when the non-volatile components of the core resin composition are taken as 100% by mass is defined as C core Then, B core / C core The photosensitive resin composition set according to any one of [1] to [4], wherein [6] The content of component (B) when the non-volatile components of the core resin composition are 100% by mass is B core The content of component (D) when the non-volatile components of the core resin composition are taken as 100% by mass is defined as D core Then, B core / D core The photosensitive resin composition set according to any one of [1] to [5], wherein [7] The content of component (B) when the non-volatile components of the cladding resin composition are 100% by mass is B clad The content of component (C) when the non-volatile components of the clad resin composition are taken as 100 mass % is C clad Then, B clad / C clad The photosensitive resin composition set according to any one of [1] to [6], wherein the ratio is 0.1 or more and 5 or less. [8] The content of component (B) when the non-volatile components of the cladding resin composition are 100 mass% is B clad The content of component (D) when the non-volatile components of the clad resin composition are taken as 100 mass % is defined as D clad Then, B clad / D clad The photosensitive resin composition set according to any one of [1] to [7], wherein [9] The photosensitive resin composition set according to any one of [1] to [8], which is a photosensitive resin composition set for producing an optical waveguide.

[10] The photosensitive resin composition set according to any one of [1] to [9], which is a photosensitive resin composition set for producing an optical waveguide capable of transmitting light having a wavelength of 1,300 nm to 1,320 nm.

[11] The photosensitive resin composition set according to any one of [1] to

[10] , which is a photosensitive resin composition set for producing a single-mode optical waveguide.

[12] A photosensitive resin sheet set including a core resin sheet and a clad resin sheet, the core resin sheet is provided with a resin composition layer containing the core resin composition in the photosensitive resin composition set according to any one of [1] to

[11] ; A photosensitive resin sheet set, the cladding resin sheet comprising a resin composition layer containing the cladding resin composition in the photosensitive resin composition set according to any one of [1] to

[11] .

[13] An optical waveguide having a core layer and a clad layer, The cladding layer is (A) a high molecular weight component having a glass transition temperature of 65° C. or lower and a weight average molecular weight of 1,500 or more and less than 14,000; (B) a resin containing a carboxyl group; (C) epoxy resin, (D) a photocurable resin, and (E) A cured product of a cladding resin composition containing a photopolymerization initiator, The core layer is (B) a resin containing a carboxyl group; (C) epoxy resin, (D) a photocurable resin, and (E) a photopolymerization initiator; and a cured product of the core resin composition, The content (mass%) of component (A) in the clad resin composition is defined as A when the non-volatile components of the clad resin composition are defined as 100 mass%. clad The content (mass%) of component (A) in the core resin composition is defined as A when the non-volatile components of the core resin composition are defined as 100 mass%. core Then, Aclad -A core An optical waveguide having a refractive index of 0.6 or more and 12 or less.

[14] An optical / electrical hybrid board comprising the optical waveguide described in

[13] .

[15] A step of forming a first composition layer containing a cladding resin composition; curing the first composition layer; forming a second composition layer containing a core resin composition on the first composition layer; a step of subjecting the second composition layer to an exposure treatment; subjecting the second composition layer to a development treatment; curing the second composition layer; forming a third composition layer containing a cladding resin composition on the second composition layer; and curing the third composition layer, in this order, At least the cladding resin composition is (A) a high molecular weight component having a glass transition temperature of 65° C. or lower and a weight average molecular weight of 1,500 or more and less than 14,000; Including, The core resin composition and the clad resin composition each comprise: (B) a resin containing a carboxyl group; (C) epoxy resin, (D) a photocurable resin, and (E) a photopolymerization initiator, The content (mass%) of component (A) in the clad resin composition is defined as A when the non-volatile components of the clad resin composition are defined as 100 mass%. clad The content (mass%) of component (A) in the core resin composition is defined as A when the non-volatile components of the core resin composition are defined as 100 mass%. core Then, A clad -A core A method for manufacturing an optical waveguide, wherein

[16] A step of forming a first composition layer containing a cladding resin composition; curing the first composition layer; forming a second composition layer containing a core resin composition on the first composition layer; a step of subjecting the second composition layer to an exposure treatment; subjecting the second composition layer to a development treatment; curing the second composition layer; forming a third composition layer containing a cladding resin composition on the second composition layer; and curing the third composition layer in this order, At least the cladding resin composition is (A) a high molecular weight component having a glass transition temperature of 65° C. or lower and a weight average molecular weight of 1,500 or more and less than 14,000; Including, The core resin composition and the clad resin composition each comprise: (B) a resin containing a carboxyl group; (C) epoxy resin, (D) a photocurable resin, and (E) a photopolymerization initiator, The content (mass%) of component (A) in the clad resin composition is defined as A when the non-volatile components of the clad resin composition are defined as 100 mass%. clad The content (mass%) of component (A) in the core resin composition is defined as A when the non-volatile components of the core resin composition are defined as 100 mass%. core Then, A clad -A core A method for manufacturing an optical / electrical hybrid board, in which Effect of the Invention

[0011] According to the present invention, it is possible to provide a photosensitive resin composition set capable of producing an optical waveguide having excellent developability and adhesion, a small difference in shrinkage rate, and small optical transmission loss; a photosensitive resin sheet set; an optical waveguide; a method for producing an optical waveguide; an optical-electrical hybrid board; and a method for producing an optical-electrical hybrid board. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a perspective view showing a schematic configuration of an optical waveguide according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view for illustrating step (I) of the method for producing an optical waveguide according to one embodiment of the present invention. [Diagram 3] FIG. 3 is a schematic cross-sectional view for illustrating step (II) of the method for producing an optical waveguide according to one embodiment of the present invention. [Figure 4] FIG. 4 is a schematic cross-sectional view for illustrating step (III) of the method for producing an optical waveguide according to one embodiment of the present invention. [Diagram 5] FIG. 5 is a schematic cross-sectional view for illustrating step (IV) of the method for producing an optical waveguide according to one embodiment of the present invention. [Figure 6] FIG. 6 is a schematic cross-sectional view for illustrating step (V) of the method for producing an optical waveguide according to one embodiment of the present invention. [Figure 7] FIG. 7 is a schematic cross-sectional view for illustrating step (VI) of the method for producing an optical waveguide according to one embodiment of the present invention. [Figure 8] FIG. 8 is a schematic cross-sectional view for explaining the step (VII) of the method for producing an optical waveguide according to one embodiment of the present invention. [Figure 9] FIG. 9 is a schematic cross-sectional view for explaining step (VIII) of the method for producing an optical waveguide according to one embodiment of the present invention. [Figure 10] FIG. 10 is a schematic cross-sectional view for explaining step (IX) of the method for producing an optical waveguide according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The photosensitive resin composition set, photosensitive resin sheet set, optical waveguide using them, a method for producing an optical waveguide, an opto-electrical hybrid board, and a method for producing an opto-electrical hybrid board of the present invention will be described in detail below.

[0014] [Photosensitive resin composition set] The photosensitive resin composition set of the present invention includes a core resin composition and a clad resin composition. The core resin composition can be suitably used as a photosensitive resin composition for forming a core layer of an optical waveguide, and the clad resin composition can be suitably used as a photosensitive resin composition for forming a clad layer of an optical waveguide. The photosensitive resin composition set can be used for the production of an optical waveguide including a core layer containing a cured product of the core resin composition and a clad layer containing a cured product of the clad resin composition.

[0015] The cladding resin composition of the present invention contains (A) a high molecular weight component having a glass transition temperature of 65° C. or lower and a weight average molecular weight of 1500 or more and less than 14000, (B) a resin containing a carboxyl group, (C) an epoxy resin, (D) a photocurable resin, and (E) a photopolymerization initiator. The core resin composition contains (B) a resin containing a carboxyl group, (C) an epoxy resin, (D) a photocurable resin, and (E) a photopolymerization initiator. The core resin composition may contain component (A) as an optional component. A is the content (mass%) of component (A) in the cladding resin composition when the nonvolatile components of the cladding resin composition are taken as 100 mass%. clad The content (mass%) of component (A) in the core resin composition is defined as A when the non-volatile components of the core resin composition are defined as 100 mass%. core Then, A clad -A core is 0.6 or more and 12 or less. With such a photosensitive resin composition set, an optical waveguide having excellent adhesion to plating and small optical transmission loss can be manufactured. In addition, the difference between the shrinkage rate of the core resin composition and the shrinkage rate of the cured product of the clad resin composition is usually small, so that depressions after desmearing are suppressed, and the rate of change in optical transmission loss before and after high temperature and high humidity environmental testing (HAST testing) is small. In addition, since the core and clad resin compositions are photosensitive resin compositions, they have excellent developability.

[0016] The clad resin composition contains (A) a high molecular weight component having a glass transition temperature of 65°C or lower and a weight average molecular weight of 1500 or more and less than 14000, (B) a resin containing a carboxyl group, (C) an epoxy resin, (D) a photocurable resin, and (E) a photopolymerization initiator, and the core resin composition contains (B) a resin containing a carboxyl group, (C) an epoxy resin, (D) a photocurable resin, and (E) a photopolymerization initiator. These resin compositions are A clad -A core The types of components and / or their blending ratios are different so that the ratio is 0.6 or more and 12 or less. The clad resin composition may further contain optional components such as (F) a curing accelerator, (G) a solvent, and (H) other additives, as necessary. The core resin composition may further contain optional components such as (A) a high molecular weight component having a glass transition temperature of 65° C. or less and a weight average molecular weight of 1500 or more and less than 14000, (F) a curing accelerator, (G) a solvent, and (H) other additives, as necessary. Each component contained in the core and clad resin compositions will be described in detail below. Hereinafter, the core resin composition and the clad resin composition will be collectively referred to simply as the "resin composition".

[0017] <(A) High molecular weight component having a glass transition temperature of 65° C. or lower and a weight average molecular weight of 1,500 or more and less than 14,000> The clad resin composition contains, as component (A), a high molecular weight component having a glass transition temperature of 65°C or less and a weight average molecular weight of 1500 or more and less than 14000. The core resin composition may contain component (A) as an optional component. By including component (A) in the resin composition, high adhesion can be obtained when a conductor layer is formed by plating on the surface of the cured product after roughening treatment. The component (A) may be used alone or in combination of two or more.

[0018] From the viewpoint of obtaining a cured product having excellent adhesion, the weight average molecular weight of the (A) component is 1500 or more, preferably 1800 or more, more preferably 2000 or more, or 3000 or more. The upper limit is less than 14000, preferably 10000 or less, more preferably 8000 or less, and even more preferably 5000 or less. The weight average molecular weight of the (A) component is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC).

[0019] From the viewpoint of obtaining a cured product having excellent adhesion, the glass transition temperature (Tg) of the (A) component is 65° C. or lower, preferably 60° C. or lower, more preferably 50° C. or lower, 40° C. or lower, 30° C. or lower, 20° C. or lower, 10° C. or lower, 0° C. or lower, −10° C. or lower, −20° C. or lower, −30° C. or lower, −35° C. or lower, or −40° C. or lower. The lower limit is preferably −100° C. or higher, more preferably −80° C. or higher, and even more preferably −75° C. or higher. The glass transition temperature (Tg) can be measured by differential scanning calorimetry at a heating rate of 5° C. / min according to JIS K7121.

[0020] As the (A) component, those having a glass transition temperature and a weight average molecular weight within the above-mentioned ranges can be used. Examples of such components include (meth)acrylic resins, polyester resins, polyurethane resins, polyether resins, polyolefin resins, and other resins. The term "(meth)acrylic resin" includes acrylic acid, methacrylic acid, and combinations thereof.

[0021] In addition, from the viewpoint of improving adhesion, the (A) component preferably has a functional group capable of reacting with the (C) epoxy resin described below. Examples of the functional group include a carboxyl group, a hydroxyl group, an epoxy group, and a (meth)acryloyl group. Among these, the functional group preferably has one or more functional groups selected from a carboxyl group, a hydroxyl group, an epoxy group, and a (meth)acryloyl group, more preferably has a functional group of either a carboxyl group or a hydroxyl group, and further preferably has a hydroxyl group.

[0022] The functional group may be present at the terminal of the (A) component or in the repeating unit. Of these, it is preferable that the functional group is present in the repeating unit. The number of functional groups per molecule of the (A) component may be one or two or more. In addition, when the (A) component contains two or more functional groups per molecule, the functional groups may be the same or different.

[0023] A preferred embodiment of the component (A) is a (meth)acrylic resin. Examples of the (meth)acrylic resin include a carboxyl group-containing (meth)acrylic resin, a hydroxyl group-containing (meth)acrylic resin, an epoxy group-containing (meth)acrylic resin, and a (meth)acryloyl group-containing (meth)acrylic resin. Among these, any of a carboxyl group-containing (meth)acrylic resin, a hydroxyl group-containing (meth)acrylic resin, and a (meth)acryloyl group-containing (meth)acrylic resin is preferred.

[0024] Examples of the main skeleton (repeating unit) of the (meth)acrylic resin include a structural unit derived from methyl acrylate (MA), a structural unit derived from ethyl acrylate (EA), a structural unit derived from ethyl methacrylate, a structural unit derived from butyl acrylate (BA), a structural unit derived from butyl methacrylate, a structural unit derived from 2-ethylhexyl acrylate (2EHA), a structural unit derived from 2-ethylhexyl methacrylate, a structural unit derived from methyl methacrylate (MMA), etc. Among these, the main skeleton of the (meth)acrylic resin is preferably any of a structural unit derived from butyl acrylate, a structural unit derived from butyl methacrylate, a structural unit derived from 2-ethylhexyl acrylate, and a structural unit derived from 2-ethylhexyl methacrylate, more preferably any of a structural unit derived from 2-ethylhexyl (meth)acrylate, and a structural unit derived from 2-ethylhexyl methacrylate, and even more preferably a structural unit derived from 2-ethylhexyl acrylate (2EHA).

[0025] Commercially available (meth)acrylic resins can be used. Commercially available (meth)acrylic resins include "CB-3060", "CB-3098", "CBB-3098", and "UT-1001" manufactured by Soken Chemical & Engineering Co., Ltd.; "BPX-003" manufactured by Negami Chemical Industries, Ltd.; and "AB-6" manufactured by Toagosei Co., Ltd.

[0026] Another preferred embodiment of the component (A) is a polyester resin, such as a carboxyl group-containing polyester resin, a hydroxyl group-containing polyester resin, an epoxy group-containing polyester resin, or a (meth)acryloyl group-containing polyester resin.

[0027] Examples of polyester resins include self-condensation products of fatty acids, and fatty acid esters which are polycondensation products of alcohols such as polyglycerin and fatty acids. Among them, the polyester resin is preferably a self-condensation product of fatty acids. The self-condensation product of fatty acids can be synthesized by heating fatty acids.

[0028] The fatty acid may have a substituent such as a hydroxy group, a halogen atom, or an alkyl group having 1 to 3 carbon atoms. Examples of the fatty acid include 12-hydroxystearic acid, stearic acid, myristic acid, montanic acid, palmitic acid, and the like, and from the viewpoint of obtaining the effects of the present invention significantly, 12-hydroxystearic acid is preferred.

[0029] The polyester resin may be a commercially available product, such as "UE-3980" manufactured by Unitika Ltd., "XA-0653" manufactured by Unitika Ltd., or "PA-111" manufactured by Ajinomoto Fine-Techno Co., Ltd.

[0030] Another preferred embodiment of the component (A) is a polyurethane resin, such as a carboxyl group-containing polyurethane resin, a hydroxyl group-containing polyurethane resin, an epoxy group-containing polyurethane resin, or a (meth)acryloyl group-containing polyurethane resin.

[0031] The polyurethane resin may be a commercially available product, such as "AGKN-026" manufactured by Negami Chemical Industries, Ltd.

[0032] When component (A) contains a carboxyl group, the acid value of component (A) is, from the viewpoint of improving resolution, preferably 10 mgKOH / g or more, more preferably 20 mgKOH / g or more, even more preferably 30 mgKOH / g or more, and is preferably 150 mgKOH / g or less, more preferably 120 mgKOH / g or less, even more preferably 100 mgKOH / g or less. The acid value can be calculated in the same manner as for the acid value of component (A).

[0033] When component (A) contains a hydroxyl group, from the viewpoint of improving resolution, the hydroxyl value of component (A) is preferably 20 mgKOH / g or more, more preferably 30 mgKOH / g or more, even more preferably 40 mgKOH / g or more, and is preferably 450 mgKOH / g or less, more preferably 200 mgKOH / g or less, even more preferably 150 mgKOH / g or less, 120 mgKOH / g or less, or 100 mgKOH / g or less. The hydroxyl value can be calculated by the following method.

[0034] First, weigh out 2 g of resin, add 5 ml of acetylation reagent (a solution of 25 g of acetic anhydride and pyridine to make 100 mL), and heat in an oil bath at 95-100°C for 1 hour. Then, add 1 mL of water and heat at 95-100°C for a further 10 minutes, then add 5 mL of ethanol. Add a few drops of phenolphthalein solution as an indicator, and titrate with 0.5 mol / L potassium hydroxide ethanol solution. The endpoint is when the indicator turns pale red for about 30 seconds. A blank test is performed in the same way, and the hydroxyl value is calculated using the following formula (1). Formula: B={(ab)×28.05 / (Wp×I)}+acid value A...(1) In the above formula (1), B represents the hydroxyl value [mgKOH / g], a represents the titration amount [mL] of the KOH solution in the blank test, b represents the titration amount [mL] of the KOH solution when the sample is used, Wp represents the mass [g] of the measured resin solution, and I represents the proportion [mass%] of the non-volatile components of the measured resin solution. The acid value A is the acid value of component (A) calculated in the same manner as the acid value of component (A).

[0035] The content of component (A) in the core resin composition, assuming the non-volatile components in the core resin composition to be 100% by mass, is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and even more preferably 0.2% by mass or more, from the viewpoint of improving adhesion to plating, and is preferably 5% by mass or less, more preferably 4% by mass or less, and even more preferably 3% by mass or less.

[0036] The content of component (A) in the clad resin composition is, from the viewpoint of promoting photocuring, preferably 0.1% by mass or more, more preferably 0.3% by mass or more, and even more preferably 0.5% by mass or more, and is preferably 10% by mass or less, more preferably 8% by mass or less, and even more preferably 7% by mass or less, 5% by mass or less, 4% by mass or less, or 3% by mass or less, assuming that the non-volatile components in the clad resin composition are 100% by mass.

[0037] In the present invention, the content of each component in the core resin composition is a value when the non-volatile components in the core resin composition are 100 mass %, unless otherwise specified, and the content of each component in the clad resin composition is a value when the non-volatile components in the clad resin composition are 100 mass %, unless otherwise specified. The non-volatile components refer to all non-volatile components in the resin composition excluding the solvent.

[0038] The content (mass%) of component (A) in the clad resin composition is defined as A when the non-volatile components of the clad resin composition are defined as 100 mass%. clad The content (mass%) of component (A) in the core resin composition is defined as A when the non-volatile components of the core resin composition are defined as 100 mass%. core Then, Aclad -A core is 0.6 or more, preferably 1 or more, more preferably 1.5 or more, and even more preferably 2 or more. The upper limit is 12 or less, preferably 10 or less, more preferably 5 or less, and even more preferably 4 or less, or 3 or less. clad -A core By adjusting the content of component (A) in the core and clad resin compositions so that the content is within this range, it becomes possible to obtain excellent developability and adhesion, reduce the difference in shrinkage rate, and further suppress an increase in optical transmission loss.

[0039] <(B) Resin containing a carboxyl group> The resin composition contains a resin containing a carboxyl group as component (B). The resin containing a carboxyl group as component (B) does not include the above-mentioned component (A). By including component (B) in the resin composition, the resolution can be improved.

[0040] As the component (B), a compound having a carboxyl group and enabling alkaline development can be used. As such a compound, a resin having both a carboxyl group and an ethylenically unsaturated group in one molecule is preferable. In other words, the component (B) is preferably a resin containing an ethylenically unsaturated group and a carboxyl group.

[0041] The ethylenically unsaturated group has a carbon-carbon double bond, and examples thereof include vinyl, allyl, propargyl, butenyl, ethynyl, phenylethynyl, maleimide, nadimide, and (meth)acryloyl groups. From the viewpoint of photoradical polymerization reactivity, (meth)acryloyl groups are preferred. The term "(meth)acryloyl group" includes methacryloyl, acryloyl, and combinations thereof. When component (B) contains an ethylenically unsaturated group, photoradical polymerization becomes possible. The number of ethylenically unsaturated groups per molecule of component (B) may be one or more. When component (B) contains two or more ethylenically unsaturated groups per molecule, the ethylenically unsaturated groups may be the same or different.

[0042] In addition, since the component (B) contains a carboxyl group, the resin composition containing the component (B) is soluble in an alkaline solution (for example, a 1% by mass aqueous solution of sodium carbonate as an alkaline developer). The number of carboxyl groups per molecule of the component (B) may be one or two or more.

[0043] One embodiment of the component (B) is an acid-modified epoxy (meth)acrylate resin.

[0044] Since the acid-modified epoxy (meth)acrylate resin has a (meth)acryloyl group, in one embodiment, photoradical polymerization may be possible. The number of (meth)acryloyl groups per molecule of the acid-modified epoxy (meth)acrylate resin may be one or two or more.

[0045] The acid-modified epoxy (meth)acrylate resin is preferably a resin that has both a (meth)acryloyl group and a carboxyl group, and that allows photoradical polymerization and alkali development.

[0046] The acid-modified epoxy (meth)acrylate resin can be produced by acid-modifying an epoxy (meth)acrylate resin by a known method. The epoxy (meth)acrylate resin can be produced, for example, by reacting an epoxy resin with acrylic acid or methacrylic acid.

[0047] The epoxy resin for producing the epoxy (meth)acrylate resin is not particularly limited as long as it is a compound having an epoxy group in the molecule, and examples thereof include bisphenol type epoxy resins such as bisphenol A type epoxy resin, hydrogenated bisphenol A type epoxy resin, bisphenol F type epoxy resin, hydrogenated bisphenol F type epoxy resin, bisphenol S type epoxy resin, and modified bisphenol F type epoxy resin obtained by reacting bisphenol F type epoxy resin with epichlorohydrin to modify it to have three or more functionalities; biphenol type epoxy resin, tetramethylbiphenol type, and other biphenol type epoxy resins; novolac type epoxy resins such as phenol novolac type epoxy resin, cresol novolac type epoxy resin, bisphenol A type novolac type epoxy resin, and alkylphenol novolac type epoxy resin; fluorine-containing epoxy resins such as bisphenol AF type epoxy resin and perfluoroalkyl type epoxy resin; naphthalene type epoxy resin, dihydroxynaphthalene type epoxy resin, polyhydroxybinaphthalene type epoxy resin, naphthol type epoxy resin, naphthol aralkyl type epoxy resin, biphenol type epoxy resin, etc. Epoxy resins having a naphthalene skeleton (epoxy resins containing a naphthalene skeleton), such as naphthol-type epoxy resins, naphthylene ether-type epoxy resins, naphthol novolac-type epoxy resins, and naphthalene-type epoxy resins obtained by the condensation reaction of polyhydroxynaphthalene with aldehydes; aralkyl-type epoxy resins; bixylenol-type epoxy resins; dicyclopentadiene-type epoxy resins; trisphenol-type epoxy resins; tert-butyl-catechol-type epoxy resins; epoxy resins containing a condensed ring skeleton, such as anthracene-type epoxy resins; glyceryl-type epoxy resins; Diglycidylamine type epoxy resins;Glycidyl ester type epoxy resins;Biphenyl type epoxy resins;Linear aliphatic epoxy resins;Epoxy resins with butadiene structure;Alicyclic epoxy resins;Heterocyclic epoxy resins;Spiro ring-containing epoxy resins;Cyclohexanedimethanol type epoxy resins;Trimethylol type epoxy resins;Tetraphenylethane type epoxy resins;Glycidyl group-containing acrylic resins such as polyglycidyl (meth)acrylate, copolymers of glycidyl methacrylate and acrylic esters;Fluorene type epoxy resins;Halogenated epoxy resins;Epoxy resins having a cardo structure;

[0048] From the viewpoint of obtaining the effect of the present invention remarkably, the epoxy resin for producing the epoxy (meth)acrylate resin is preferably an epoxy resin containing an aromatic skeleton. Here, the aromatic skeleton is a concept including polycyclic aromatics and aromatic heterocycles. Among them, the epoxy resin for producing the epoxy (meth)acrylate resin is preferably any one of an aralkyl type epoxy resin, a naphthol aralkyl type epoxy resin, and an epoxy resin having a cardo structure, and a naphthol aralkyl type epoxy resin is more preferable. The cardo structure refers to a structure in which two aromatic rings are bonded to a carbon atom inside the ring.

[0049] In one embodiment, the acid-modified epoxy (meth)acrylate resin preferably includes an acid-modified epoxy (meth)acrylate resin having a skeleton selected from an aralkyl skeleton, a naphthol aralkyl skeleton, and a cardo skeleton, and particularly preferably includes an acid-modified epoxy (meth)acrylate resin having a naphthol aralkyl skeleton.

[0050] In one embodiment, the acid-modified epoxy (meth)acrylate resin preferably contains a resin selected from an acid-modified epoxy (meth)acrylate resin in which a hydroxyl group of an epoxy (meth)acrylate resin has been esterified (hereinafter referred to as an "ester-type acid-modified epoxy (meth)acrylate resin"), and an acid-modified epoxy (meth)acrylate resin in which a hydroxyl group of an epoxy (meth)acrylate resin has been urethanized (hereinafter referred to as a "urethane-type acid-modified epoxy (meth)acrylate resin"), and particularly preferably contains an ester-type acid-modified epoxy (meth)acrylate resin.

[0051] The ester-type acid-modified epoxy (meth)acrylate resin can be produced, for example, by reacting an epoxy (meth)acrylate resin with an acid anhydride. The ester-type acid-modified epoxy (meth)acrylate resin may be used alone or in combination of two or more.

[0052] Examples of the acid anhydride include maleic anhydride, succinic anhydride, itaconic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, trimellitic anhydride, pyromellitic anhydride, and benzophenonetetracarboxylic dianhydride, and these may be used alone or in combination of two or more. Among these, succinic anhydride and tetrahydrophthalic anhydride are preferred, and tetrahydrophthalic anhydride is more preferred.

[0053] The ester-type acid-modified epoxy (meth)acrylate resin preferably contains a resin selected from a cresol novolac skeleton-containing ester-type acid-modified epoxy (meth)acrylate resin, a bisphenol A skeleton-containing ester-type acid-modified epoxy (meth)acrylate resin, a bisphenol F skeleton-containing ester-type acid-modified epoxy (meth)acrylate resin, a biphenyl skeleton-containing acid ester-type modified epoxy (meth)acrylate resin, and a naphthol aralkyl skeleton-containing ester-type acid-modified epoxy (meth)acrylate resin.

[0054] The ester-type acid-modified epoxy (meth)acrylate resin can be synthesized by a known method, but a commercially available product may also be used. Specific examples of commercially available products include "CCR-1373H" (cresol novolac skeleton-containing acid-modified epoxy acrylate resin), "ZCR-8001H" (biphenyl skeleton-containing acid-modified epoxy acrylate resin), "ZCR-1569H" (biphenyl skeleton-containing acid-modified epoxy acrylate resin), "CCR-1171H" (cresol novolac skeleton-containing acid-modified epoxy acrylate resin), "ZCR-1797H", and "ZCR-1761H" (biphenyl skeleton-containing acid-modified epoxy acrylate resin), all of which are manufactured by Nippon Kayaku Co., Ltd. Examples of suitable epoxy acrylate resins include "ZAR-2000" (acid-modified epoxy acrylate resin containing bisphenol A skeleton), "ZFR-1491H", and "ZFR-1533H" (acid-modified epoxy acrylate resin containing bisphenol F skeleton) manufactured by Nippon Kayaku Co., Ltd., "PR-300CP" (cresol novolac type acid-modified epoxy acrylate resin) manufactured by Showa Denko KK, and "CCR-1179" (cresol novolac skeleton-containing epoxy acrylate resin) manufactured by Nippon Kayaku Co., Ltd.

[0055] The urethane-type acid-modified epoxy (meth)acrylate resin can be produced, for example, by reacting an epoxy (meth)acrylate resin with a diisocyanate compound and a carboxyl group-containing diol compound. The urethane-type acid-modified epoxy (meth)acrylate resin may be used alone or in combination of two or more.

[0056] Examples of the diisocyanate compound include aromatic diisocyanate compounds such as phenylene diisocyanate, tolylene diisocyanate, xylylene diisocyanate, tetramethylxylylene diisocyanate, diphenyl diisocyanate, and naphthalene diisocyanate; and aliphatic diisocyanate compounds such as hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, isophorone diisocyanate, allylene sulfone ether diisocyanate, allyl cyanide diisocyanate, N-acyl diisocyanate, trimethylhexamethylene diisocyanate, and 1,3-bis(isocyanate methyl)cyclohexane.

[0057] Examples of the carboxy group-containing diol compound include dimethylolpropionic acid, dimethylolbutanoic acid, and dimethylolnonanoic acid.

[0058] The urethane-type acid-modified epoxy (meth)acrylate resin preferably contains a resin selected from a cresol novolac skeleton-containing urethane-type acid-modified epoxy (meth)acrylate resin, a bisphenol A skeleton-containing urethane-type acid-modified epoxy (meth)acrylate resin, a bisphenol F skeleton-containing urethane-type acid-modified epoxy (meth)acrylate resin, a biphenyl skeleton-containing acid urethane-type modified epoxy (meth)acrylate resin, and a naphthol aralkyl skeleton-containing urethane-type acid-modified epoxy (meth)acrylate resin.

[0059] The urethane-type acid-modified epoxy (meth)acrylate resin can be synthesized by a known synthesis method, but a commercially available product may also be used. Examples of known synthesis methods include the method described in JP 2016-199719 A. Specific examples of commercially available products include "UXE-3024", "UXE-3011", "UXE-3012", and "UXE-3024" manufactured by Nippon Kayaku Co., Ltd.

[0060] Another embodiment of the (B) component is an unsaturated modified (meth)acrylic resin obtained by reacting an ethylenically unsaturated group-containing epoxy compound with a (meth)acrylic resin having a structural unit obtained by polymerizing acrylic acid and / or methacrylic acid to introduce an ethylenically unsaturated group. Examples of the ethylenically unsaturated group-containing epoxy compound include glycidyl methacrylate, 4-hydroxybutyl (meth)acrylate glycidyl ether, and 3,4-epoxycyclohexylmethyl (meth)acrylate. It is also possible to react an acid anhydride with the hydroxyl group generated during the introduction of the unsaturated group. The acid anhydride may be the same as the acid anhydride described above. The term "(meth)acrylic resin" includes methacrylic resin, acrylic resin, and combinations thereof.

[0061] Such unsaturated modified (meth)acrylic resins can be commercially available products, and specific examples include "SPC-1000" and "SPC-3000" manufactured by Showa Denko K.K., and "Cyclomer P(ACA)Z-250", "Cyclomer P(ACA)Z-251", "Cyclomer P(ACA)Z-254", "Cyclomer P(ACA)Z-300", and "Cyclomer P(ACA)Z-320" manufactured by Daicel-Allnex Corporation.

[0062] From the viewpoint of improving the alkaline developability of the resin composition, the acid value of the (B) component is preferably 0.1 mgKOH / g or more, more preferably 0.5 mgKOH / g or more, even more preferably 1 mgKOH / g or more, 10 mgKOH / g or more, even more preferably 20 mgKOH / g or more, 30 mgKOH / g or more, particularly preferably 40 mgKOH / g or more, 50 mgKOH / g or more. The upper limit of the acid value of the (B) component is preferably 200 mgKOH / g or less, more preferably 150 mgKOH / g or less, even more preferably 120 mgKOH / g or less, particularly preferably 100 mgKOH / g or less.

[0063] The weight average molecular weight of the (B) component is preferably 20,000 or less, more preferably 17,000 or less, even more preferably 15,000 or less, and is preferably 500 or more, more preferably 750 or more, even more preferably 900 or more. The weight average molecular weight is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC).

[0064] The content of component (B) in the core resin composition is, from the viewpoint of improving developability, preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and preferably 40% by mass or less, even more preferably 35% by mass or less, and particularly preferably 30% by mass or less, assuming the non-volatile components of the core resin composition to be 100% by mass.

[0065] The content of component (B) in the clad resin composition is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, preferably 40% by mass or less, even more preferably 35% by mass or less, and particularly preferably 30% by mass or less, from the viewpoint of improving developability, assuming the non-volatile components of the clad resin composition to be 100% by mass.

[0066] The content (mass%) of component (B) in the core resin composition is defined as B when the non-volatile components of the core resin composition are defined as 100 mass%. core Then, B core / A core From the viewpoint of significantly obtaining the effects of the present invention, is preferably 0 or more, more preferably 1 or more, even more preferably 5 or more, 10 or more, 30 or more, 50 or more, 70 or more, or 100 or more, and is preferably 300 or less, more preferably 250 or less, even more preferably 200 or less, or 150 or less.

[0067] The content (mass%) of component (B) in the clad resin composition is defined as B when the non-volatile components of the clad resin composition are defined as 100 mass%. clad Then, B clad / A cladFrom the viewpoint of significantly obtaining the effects of the present invention, is preferably 1 or more, more preferably 1.5 or more, even more preferably 2 or more, and is preferably 100 or less, more preferably 75 or less, even more preferably 50 or less, or 40 or less.

[0068] <(C) Epoxy resin> The resin composition contains an epoxy resin as component (C). The epoxy resin (C) as component (C) does not include those corresponding to the above-mentioned components (A) and (B). By containing component (C), it is possible to improve insulation reliability. The epoxy resin (C) may be used alone or in combination of two or more kinds.

[0069] (C) Epoxy resins include, for example, bixylenol type epoxy resins; bisphenol type epoxy resins such as bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, and bisphenol AF type epoxy resins; dicyclopentadiene type epoxy resins; novolac type epoxy resins such as trisphenol type epoxy resins and phenol novolac type epoxy resins; tert-butyl-catechol type epoxy resins; naphthalene type epoxy resins, naphthol type epoxy resins, naphthol aralkyl type epoxy resins, naphthylene ether type epoxy resins, and naphthol novolac type epoxy resins. Examples of the epoxy resins include epoxy resins containing an aryl skeleton, anthracene type epoxy resins, glycidylamine type epoxy resins, glycidyl ester type epoxy resins, cresol novolac type epoxy resins, phenol aralkyl type epoxy resins, biphenyl skeleton-containing epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane type epoxy resins, cyclohexane dimethanol type epoxy resins, trimethylol type epoxy resins, tetraphenylethane type epoxy resins, isocyanurate type epoxy resins, and phenolphthalimidine type epoxy resins. Among these, the epoxy resin (C) preferably contains either a naphthalene type epoxy resin or a naphthol aralkyl type epoxy resin, from the viewpoint of obtaining the effects of the present invention significantly.

[0070] The resin composition preferably contains, as the epoxy resin (C), an epoxy resin having two or more epoxy groups in one molecule. The proportion of the epoxy resin having two or more epoxy groups in one molecule relative to 100% by mass of the epoxy resin (C) is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more.

[0071] The (C) epoxy resin includes an epoxy resin that is solid at a temperature of 20° C. (hereinafter sometimes referred to as a "solid epoxy resin") and an epoxy resin that is liquid at a temperature of 20° C. (hereinafter sometimes referred to as a "liquid epoxy resin"). The resin composition may contain, as the (C) epoxy resin, only a liquid epoxy resin, or only a solid epoxy resin, or may contain both a liquid epoxy resin and a solid epoxy resin, but it is particularly preferable that the resin composition contains only a solid epoxy resin.

[0072] As the solid epoxy resin, a solid epoxy resin having three or more epoxy groups in one molecule is preferable, and an aromatic solid epoxy resin having three or more epoxy groups in one molecule is more preferable.

[0073] As the solid epoxy resin, bixylenol type epoxy resin, naphthalene type epoxy resin, naphthol aralkyl type epoxy resin, naphthalene type tetrafunctional epoxy resin, naphthol novolac type epoxy resin, cresol novolac type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol type epoxy resin, biphenyl type epoxy resin, naphthylene ether type epoxy resin, anthracene type epoxy resin, bisphenol A type epoxy resin, bisphenol AF type epoxy resin, phenol aralkyl type epoxy resin, tetraphenylethane type epoxy resin, phenolphthalimidine type epoxy resin are preferred, and it is preferred to contain either a naphthalene type epoxy resin or a naphthol aralkyl type epoxy resin.

[0074] Specific examples of solid epoxy resins include "HP4032H" (naphthalene type epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene type tetrafunctional epoxy resins) manufactured by DIC Corporation; "N-690" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "N-673" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "HP-7200", "HP-7200HH", "HP-7200H", and "HP-7200L" manufactured by DIC Corporation. (Dicyclopentadiene type epoxy resin); "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", and "HP6000" (naphthylene ether type epoxy resin) manufactured by DIC; "EPPN-502H" (trisphenol type epoxy resin) manufactured by Nippon Kayaku; "NC7000L" (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku; "NC3000H", "NC3000", "NC3000L", "NC3000FH", and "NC3100" (biphenyl type epoxy resin); "ESN475V", "ESN4100V" (naphthalene type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ESN485" (naphthol type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ESN375" (dihydroxynaphthalene type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YX4000H", "YX4000", "YX4000HK", "YL7890" (bixylenol type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YL6121" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical; "YX7700" (phenol aralkyl type epoxy resin) manufactured by Mitsubishi Chemical; "PG-100" and "CG-500" manufactured by Osaka Gas Chemical; "YL7760" (bisphenol AF type epoxy resin) manufactured by Mitsubishi Chemical; "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical; "jER1010" (bisphenol A type epoxy resin) manufactured by Mitsubishi Chemical; "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical;Examples of such resins include "WHR991S" (phenolphthalimidine type epoxy resin) manufactured by Nippon Kayaku Co., Ltd. These resins may be used alone or in combination of two or more.

[0075] The liquid epoxy resin is preferably a liquid epoxy resin having two or more epoxy groups in one molecule.

[0076] As the liquid epoxy resin, glycirol type epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin, phenol novolac type epoxy resin, alicyclic epoxy resin having an ester skeleton, cyclohexane dimethanol type epoxy resin, cyclic aliphatic glycidyl ether, and epoxy resin having a butadiene structure are preferred.

[0077] Specific examples of liquid epoxy resins include "EX-992L" manufactured by Nagase ChemteX Corporation, "YX7400" manufactured by Mitsubishi Chemical Corporation, "HP4032", "HP4032D", and "HP4032SS" (naphthalene type epoxy resins) manufactured by DIC Corporation; "828US", "jER828EL", "828EL", "825", and "Epikote 828EL" (bisphenol A type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER807" and "1750" ( bisphenol F type epoxy resin; "jER152" (phenol novolac type epoxy resin) manufactured by Mitsubishi Chemical; "630", "630LSD", "604" (glycidylamine type epoxy resin) manufactured by Mitsubishi Chemical; "ED-523T" (glycirol type epoxy resin) manufactured by ADEKA; "EP-3950L", "EP-3980S" (glycidylamine type epoxy resin) manufactured by ADEKA; "EP-4088S" (dicyclopentadiene type epoxy resin) manufactured by ADEKA; "ZX1059" (mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) manufactured by Nippon Steel Chemical & Material; "EX-721" (glycidyl ester type epoxy resin) manufactured by Nagase ChemteX; "EX-991L" (alkyleneoxy and butadiene type epoxy resin) manufactured by Nagase ChemteX; "Celloxide 2021P" (alicyclic epoxy resin with ester structure) manufactured by Daicel ); "PB-3600" manufactured by Daicel Corporation, "JP-100" and "JP-200" manufactured by Nippon Soda Co., Ltd. (epoxy resins having a butadiene structure); "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane type epoxy resins) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "EG-280" (fluorene structure-containing epoxy resin) manufactured by Osaka Gas Chemicals Co., Ltd.; and "EX-201" (cyclic aliphatic glycidyl ether) manufactured by Nagase ChemteX Corporation.

[0078] When a solid epoxy resin and a liquid epoxy resin are used in combination as the (C) epoxy resin, the mass ratio thereof (solid epoxy resin:liquid epoxy resin) is preferably 10:1 to 1:50, more preferably 5:1 to 1:20, and particularly preferably 2:1 to 1:10.

[0079] The epoxy equivalent of the (C) epoxy resin is preferably 50 g / eq. to 5,000 g / eq., more preferably 60 g / eq. to 2,000 g / eq., even more preferably 70 g / eq. to 1,000 g / eq., and even more preferably 80 g / eq. to 500 g / eq. The epoxy equivalent is the mass of the resin per equivalent of epoxy group. This epoxy equivalent can be measured according to JIS K7236.

[0080] The weight average molecular weight (Mw) of the epoxy resin (C) is preferably from 100 to 5,000, more preferably from 250 to 3,000, and further preferably from 400 to 1500. The weight average molecular weight of the resin can be measured by gel permeation chromatography (GPC) as a polystyrene-equivalent value.

[0081] The content of the (C) epoxy resin in the core resin composition is, from the viewpoint of significantly obtaining the effects of the present invention, preferably 10 mass % or more, more preferably 20 mass % or more, even more preferably 25 mass % or more, or 30 mass % or more, and is preferably 50 mass % or less, more preferably 45 mass % or less, and even more preferably 40 mass % or less, assuming the non-volatile components of the core resin composition to be 100 mass %, inclusive.

[0082] The content of the (C) epoxy resin in the clad resin composition is preferably 20% by mass or more, more preferably 25% by mass or more, and even more preferably 30% by mass or more, and is preferably 50% by mass or less, more preferably 45% by mass or less, and even more preferably 40% by mass or less, from the viewpoint of significantly obtaining the effects of the present invention, assuming the non-volatile components of the clad resin composition to be 100% by mass.

[0083] The content of component (C) when the non-volatile components of the core resin composition are 100% by mass is C core Then, B core / C coreFrom the viewpoint of obtaining the effects of the present invention significantly, is preferably 0.1 or more, more preferably 0.3 or more, even more preferably 0.5 or more, and is preferably 5 or less, more preferably 3 or less, even more preferably 1 or less.

[0084] The content of component (C) when the non-volatile components of the cladding resin composition are 100 mass % is C clad Then, B clad / C clad From the viewpoint of obtaining the effects of the present invention significantly, is preferably 0.1 or more, more preferably 0.3 or more, even more preferably 0.5 or more, and is preferably 5 or less, more preferably 3 or less, even more preferably 1 or less.

[0085] <(D) Photocurable resin> The resin composition contains a photocurable resin (D) as the component (D). The photocurable resin (D) as the component (D) does not include those corresponding to the above-mentioned components (A) to (C). By including the component (D) in the resin composition, the photoreactivity during exposure can be improved. The component (D) may be used alone or in combination of two or more.

[0086] As the component (D), for example, a (meth)acrylate compound having one or more (preferably two or more) (meth)acryloyl groups in one molecule can be used.

[0087] Examples of the (meth)acrylate compound include hydroxyalkyl acrylates such as 2-hydroxyethyl acrylate and 2-hydroxybutyl acrylate; mono- or diacrylates of glycols such as ethylene glycol, methoxytetraethylene glycol, polyethylene glycol, and propylene glycol; acrylamides such as N,N-dimethylacrylamide and N-methylolacrylamide; aminoalkyl acrylates such as N,N-dimethylaminoethyl acrylate; polyhydric alcohols such as trimethylolpropane, pentaerythritol, and dipentaerythritol, or polyhydric acrylates of their ethylene oxide, propylene oxide, or ε-caprolactone adducts; phenols such as phenoxy acrylate and phenoxyethyl acrylate, or acrylates such as their ethylene oxide or propylene oxide adducts; epoxy acrylates derived from glycidyl ethers such as trimethylolpropane triglycidyl ether, modified epoxy acrylates, melamine acrylates, and / or methacrylates corresponding to the above acrylates.Among these, polyvalent acrylates or polyvalent methacrylates are preferred. For example, trivalent acrylates or methacrylates include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane EO-added tri(meth)acrylate, glycerin PO-added tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, tetrafurfuryl alcohol oligo(meth)acrylate, ethyl carbitol oligo(meth)acrylate, 1,4-butanediol oligo(meth)acrylate, 1,6-hexanediol oligo(meth)acrylate, trimethylolpropane oligo(meth)acrylate, pentaerythritol oligo(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, Examples of the photosensitive (meth)acrylate compounds include hexa(meth)acrylate and (meth)acrylic acid ester of N,N,N',N'-tetrakis(β-hydroxyethyl)ethyldiamine, and examples of the acrylates or methacrylates having a valence of three or more include phosphoric acid triester (meth)acrylates such as tri(2-(meth)acryloyloxyethyl)phosphate, tri(2-(meth)acryloyloxypropyl)phosphate, tri(3-(meth)acryloyloxypropyl)phosphate, tri(3-(meth)acryloyl-2-hydroxyloxypropyl)phosphate, di(3-(meth)acryloyl-2-hydroxyloxypropyl)(2-(meth)acryloyloxyethyl)phosphate, and (3-(meth)acryloyl-2-hydroxyloxypropyl)di(2-(meth)acryloyloxyethyl)phosphate. These photosensitive (meth)acrylate compounds may be used alone or in combination of two or more. "EO" refers to ethylene oxide.

[0088] As the component (D), commercially available products can be used, such as "DPHA" manufactured by Nippon Kayaku Co., Ltd. and "EBECRYL3708" manufactured by Daicel Allnex Corporation.

[0089] Component (D) usually has a low viscosity. The specific viscosity of component (D) is usually less than 0.5 Pa s. There is no particular lower limit to the viscosity of component (D), and it can be, for example, 0.001 Pa s or more, 0.005 Pa s or more, or 0.01 Pa s or more. The viscosity of component (D) can be measured using an E-type viscometer at 25±2°C.

[0090] The content of component (D) in the core resin composition is, from the viewpoint of promoting photocuring, preferably 15% by mass or more, more preferably 20% by mass or more, even more preferably 25% by mass or more, and is preferably 50% by mass or less, more preferably 45% by mass or less, even more preferably 40% by mass or less, assuming the non-volatile components in the core resin composition to be 100% by mass.

[0091] The content of component (D) in the clad resin composition is, from the viewpoint of promoting photocuring, preferably 15% by mass or more, more preferably 20% by mass or more, even more preferably 25% by mass or more, and is preferably 50% by mass or less, more preferably 45% by mass or less, even more preferably 40% by mass or less, assuming that the non-volatile components in the clad resin composition are 100% by mass.

[0092] The content of component (D) when the non-volatile components of the core resin composition are taken as 100% by mass is D core Then, B core / D core From the viewpoint of obtaining the effects of the present invention significantly, is preferably 0.1 or more, more preferably 0.3 or more, even more preferably 0.5 or more, and is preferably 3 or less, more preferably 2 or less, even more preferably 1 or less.

[0093] The content of component (D) when the non-volatile components of the clad resin composition are taken as 100% by mass is D clad Then, B clad / D clad From the viewpoint of obtaining the effects of the present invention significantly, is preferably 0.1 or more, more preferably 0.3 or more, even more preferably 0.5 or more, and is preferably 3 or less, more preferably 2 or less, even more preferably 1 or less.

[0094] D clad / D core From the viewpoint of obtaining the effects of the present invention significantly, D is preferably 0.1 or more, more preferably 0.3 or more, even more preferably 0.5 or more, or 0.8 or more, and is preferably 3 or less, more preferably 2 or less, even more preferably 1.5 or less. clad / D core By adjusting the content of the (D) component in the core and cladding resin compositions so that the content falls within this range, the change in shrinkage rate is suppressed, and as a result, it is possible to suppress an increase in optical transmission loss.

[0095] <(E) Photopolymerization initiator> The resin composition contains a photopolymerization initiator as component (E). The photopolymerization initiator (E) as component (E) does not include those corresponding to the above-mentioned components (A) to (D). By including the photopolymerization initiator (E) in the resin composition, the resin composition can be efficiently photocured. The component (E) may be used alone or in combination of two or more.

[0096] (E) The photopolymerization initiator may be any compound, and examples thereof include acylphosphine oxide-based photopolymerization initiators such as bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide and 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide; oxime ester-based photopolymerization initiators such as 1,2-octanedione, 1-4-(phenylthio)-2-(O-benzoyloxime), ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, and 1-(O-acetyloxime); 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-[4-(4-morpholinyl)phenyl]-1-butanone, and 2-methyl-1-[4-(methyl α-aminoalkylphenone-based photopolymerization initiators such as ... Among these, from the viewpoint of more efficiently photocuring the resin composition, either an acylphosphine oxide-based photopolymerization initiator or an oxime ester-based photopolymerization initiator is preferred, with an acylphosphine oxide-based photopolymerization initiator being more preferred.

[0097] Specific examples of the (E) photopolymerization initiator include "Omnirad907", "Omnirad369", "Omnirad379", "Omnirad819", and "OmniradTPO" manufactured by IGM Resins, "IrgacureOXE-01", "IrgacureOXE-02", "IrgacureTPO", and "Irgacure819" manufactured by BASF, and "N-1919" manufactured by ADEKA.

[0098] The content of the (E) photopolymerization initiator in the core resin composition is preferably 1% by mass or more, more preferably 1.5% by mass or more, and even more preferably 2% by mass or more, when the non-volatile components of the core resin composition are taken as 100% by mass, from the viewpoint of sufficiently photocuring the core resin composition. On the other hand, from the viewpoint of suppressing a decrease in developability due to excessive sensitivity, the upper limit is preferably 10% by mass or less, more preferably 8% by mass or less, and even more preferably 5% by mass or less.

[0099] The content of the photopolymerization initiator (E) in the clad resin composition is preferably 1% by mass or more, more preferably 1.5% by mass or more, and even more preferably 2% by mass or more, based on 100% by mass of the nonvolatile components of the clad resin composition, from the viewpoint of sufficiently photocuring the clad resin composition. On the other hand, from the viewpoint of suppressing a decrease in developability due to excessive sensitivity, the upper limit is preferably 10% by mass or less, more preferably 8% by mass or less, and even more preferably 5% by mass or less.

[0100] The content of component (E) when the non-volatile components of the core resin composition are 100% by mass is E core Then, B core / E core From the viewpoint of significantly obtaining the effects of the present invention, is preferably 1 or more, more preferably 3 or more, even more preferably 5 or more, and is preferably 20 or less, more preferably 15 or less, even more preferably 10 or less.

[0101] The content of component (E) when the non-volatile components of the cladding resin composition are 100% by mass is E clad Then, Bclad / E clad From the viewpoint of significantly obtaining the effects of the present invention, is preferably 1 or more, more preferably 3 or more, even more preferably 5 or more, and is preferably 20 or less, more preferably 15 or less, even more preferably 10 or less.

[0102] The resin composition may further contain, in combination with the component (E), tertiary amines such as N,N-dimethylaminobenzoic acid ethyl ester, N,N-dimethylaminobenzoic acid isoamyl ester, pentyl-4-dimethylaminobenzoate, triethylamine, triethanolamine, etc. as photopolymerization initiator assistants, or may contain photosensitizers such as pyrarizones, anthracenes, coumarins, xanthones, thioxanthones, etc. Any of these may be used alone or in combination of two or more.

[0103] <(F) Curing accelerator> The resin composition may contain a curing accelerator (F) as an optional component. The curing accelerator (F) as the component (F) does not include those corresponding to the above-mentioned components (A) to (E). The curing accelerator (F) functions as a catalyst for the reaction of the components such as the epoxy resin (C) contained in the resin composition, and can accelerate the curing of the resin composition.

[0104] Examples of the curing accelerator include imidazole-based curing accelerators, phosphorus-based curing accelerators, urea-based curing accelerators, guanidine-based curing accelerators, metal-based curing accelerators, and amine-based curing accelerators. Among these, imidazole-based curing accelerators are preferred. (F) The curing accelerator may be used alone or in combination of two or more.

[0105] Examples of the imidazole-based curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, and 1-benzyl-2-methylimidazole. Phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl -(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct , 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, 2-phenylimidazoline, and other imidazole compounds and adducts of imidazole compounds and epoxy resins. Commercially available imidazole curing accelerators include, for example, "1B2PZ", "2E4MZ", "2MZA-PW", "2MZ-OK", "2MA-OK", "2MA-OK-PW", "2PHZ", "2PHZ-PW", "Cl1Z", "Cl1Z-CN", "Cl1Z-CNS", and "C11Z-A" manufactured by Shikoku Chemical Industry Co., Ltd.; and "P200-H50" manufactured by Mitsubishi Chemical Corporation.

[0106] Examples of the phosphorus-based curing accelerator include aliphatic phosphonium salts such as tetrabutyl phosphonium bromide, tetrabutyl phosphonium chloride, tetrabutyl phosphonium acetate, tetrabutyl phosphonium decanoate, tetrabutyl phosphonium laurate, bis(tetrabutyl phosphonium)pyromellitate, tetrabutyl phosphonium hydrogenhexahydrophthalate, tetrabutyl phosphonium 2,6-bis[(2-hydroxy-5-methylphenyl)methyl]-4-methylphenolate, and di-tert-butyldimethylphosphonium tetraphenylborate; methyl triphenyl phosphonium bromide, ethyl triphenyl phosphonium bromide, propyl triphenyl phosphonium bromide, butyl triphenyl phosphonium bromide, benzyl triphenyl phosphonium chloride, tetraphenyl phosphonium bromide, p-tolyl triphenyl phosphonium tetra-p-tolylborate, tetraphenyl phosphonium bromide, and the like. aromatic phosphonium salts such as tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, triphenylethylphosphonium tetraphenylborate, tris(3-methylphenyl)ethylphosphonium tetraphenylborate, tris(2-methoxyphenyl)ethylphosphonium tetraphenylborate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate; aromatic phosphine-borane complexes such as triphenylphosphine-triphenylborane; aromatic phosphine-quinone adducts such as triphenylphosphine-p-benzoquinone adduct; aliphatic phosphines such as tributylphosphine, tri-tert-butylphosphine, trioctylphosphine, di-tert-butyl(2-butenyl)phosphine, di-tert-butyl(3-methyl-2-butenyl)phosphine, and tricyclohexylphosphine;Dibutylphenylphosphine, di-tert-butylphenylphosphine, methyldiphenylphosphine, ethyldiphenylphosphine, butyldiphenylphosphine, diphenylcyclohexylphosphine, triphenylphosphine, tri-o-tolylphosphine, tri-m-tolylphosphine, tri-p-tolylphosphine, tris(4-ethylphenyl)phosphine, tris(4-propylphenyl)phosphine, tris(4-isopropylphenyl)phosphine, tris(4-butylphenyl)phosphine, tris(4-tert-butylphenyl)phosphine, tris(2,4-dimethylphenyl)phosphine, tris(2,5-dimethylphenyl)phosphine, tris(2,6-dimethylphenyl)phosphine Examples of aromatic phosphines include tris(3,5-dimethylphenyl)phosphine, tris(2,4,6-trimethylphenyl)phosphine, tris(2,6-dimethyl-4-ethoxyphenyl)phosphine, tris(2-methoxyphenyl)phosphine, tris(4-methoxyphenyl)phosphine, tris(4-ethoxyphenyl)phosphine, tris(4-tert-butoxyphenyl)phosphine, diphenyl-2-pyridylphosphine, 1,2-bis(diphenylphosphino)ethane, 1,3-bis(diphenylphosphino)propane, 1,4-bis(diphenylphosphino)butane, 1,2-bis(diphenylphosphino)acetylene, and 2,2'-bis(diphenylphosphino)diphenyl ether.

[0107] Examples of the urea-based curing accelerator include 1,1-dimethylurea; aliphatic dimethylureas such as 1,1,3-trimethylurea, 3-ethyl-1,1-dimethylurea, 3-cyclohexyl-1,1-dimethylurea, and 3-cyclooctyl-1,1-dimethylurea; 3-phenyl-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, 3-(3-chloro-4-methylphenyl)-1,1-dimethylurea, 3-(2-methylphenyl)-1,1-dimethylurea, 3-(4-methylphenyl)-1,1-dimethylurea, and 3-(3,4-dimethylphenyl)-1,1-dimethylurea. aromatic dimethylureas such as butylurea, 3-(4-isopropylphenyl)-1,1-dimethylurea, 3-(4-methoxyphenyl)-1,1-dimethylurea, 3-(4-nitrophenyl)-1,1-dimethylurea, 3-[4-(4-methoxyphenoxy)phenyl]-1,1-dimethylurea, 3-[4-(4-chlorophenoxy)phenyl]-1,1-dimethylurea, 3-[3-(trifluoromethyl)phenyl]-1,1-dimethylurea, N,N-(1,4-phenylene)bis(N',N'-dimethylurea), and N,N-(4-methyl-1,3-phenylene)bis(N',N'-dimethylurea) [toluene bisdimethylurea].

[0108] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide.

[0109] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.

[0110] Examples of the amine-based curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, 1,8-diazabicyclo(5,4,0)-undecene, etc. Commercially available amine-based curing accelerators may be used, such as "MY-25" manufactured by Ajinomoto Fine-Techno Co., Ltd.

[0111] The content of component (F) in the core resin composition is, from the viewpoint of promoting photocuring, preferably 0.1 mass % or more, more preferably 0.2 mass % or more, even more preferably 0.3 mass % or more, and is preferably 1.5 mass % or less, more preferably 1 mass % or less, even more preferably 0.8 mass % or less, assuming the non-volatile components in the core resin composition to be 100 mass %, inclusive.

[0112] The content of component (F) in the clad resin composition is preferably 0.1 mass % or more, more preferably 0.2 mass % or more, and even more preferably 0.3 mass % or more, and is preferably 1.5 mass % or less, more preferably 1 mass % or less, and even more preferably 0.8 mass % or less, from the viewpoint of promoting photocuring, assuming the non-volatile components in the clad resin composition to be 100 mass %.

[0113] <(G) Solvent> The resin composition may further contain a (G) solvent as an optional component. By including the (G) solvent, the viscosity of the varnish can be adjusted. Examples of the (G) solvent include organic solvents.

[0114] Examples of the (G) solvent include ketones such as ethyl methyl ketone (MEK) and cyclohexanone; aromatic hydrocarbons such as toluene, xylene, and tetramethylbenzene; glycol ethers such as diethylene glycol monoethyl ether acetate, ethyl diglycol acetate (EDGAc), methyl cellosolve, butyl cellosolve, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol diethyl ether, and triethylene glycol monoethyl ether; esters such as ethyl acetate, butyl acetate, butyl cellosolve acetate, carbitol acetate, and ethyl diglycol acetate; aliphatic hydrocarbons such as octane and decane; and petroleum-based solvents such as petroleum ether, petroleum naphtha, hydrogenated petroleum naphtha, and solvent naphtha. These are used alone or in combination of two or more. The content of the solvent when used can be appropriately adjusted from the viewpoint of the coating property of the resin composition.

[0115] <(H) Other Additives> The resin composition may further contain (H) other additives to the extent that the object of the present invention is not impaired. Examples of (H) other additives include inorganic fillers, organic fillers, fine particles such as melamine and organic bentonite, colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium oxide, carbon black and naphthalene black, polymerization inhibitors such as hydroquinone, phenothiazine, methylhydroquinone, hydroquinone monomethyl ether, catechol and pyrogallol, thickeners such as bentone and montmorillonite, silicone-based, fluorine-based and vinyl resin-based defoamers, thermosetting resins such as phenol-based curing agents and cyanate ester-based curing agents, and the like.

[0116] The resin composition can be produced by mixing the above-mentioned components (A) to (E) as essential components, appropriately mixing the above-mentioned components (F) to (H) as optional components, and kneading or stirring, as necessary, with kneading means such as a triple roll mill, a ball mill, a bead mill, or a sand mill, or with stirring means such as a super mixer or a planetary mixer.

[0117] <Physical properties of the photosensitive resin composition set> The refractive index of the cured product obtained by heating the core resin composition at 190° C. for 90 minutes is preferably 1.3 or more, more preferably 1.4 or more, and even more preferably 1.5 or more, and is preferably 2 or less, more preferably 1.9 or less, and even more preferably 1.8 or less. The refractive index can be measured according to the method described in the Examples below.

[0118] The refractive index of the cured product obtained by heating the cladding resin composition at 190° C. for 90 minutes is preferably 1.3 or more, more preferably 1.4 or more, and even more preferably 1.5 or more, and is preferably 2 or less, more preferably 1.9 or less, and even more preferably 1.8 or less. The refractive index can be measured according to the method described in the Examples below.

[0119] The cured product of the cladding resin composition and the cured product of the core resin composition have a refractive index n such that the numerical aperture NA, represented by the following formula (1), falls within a specific range. core and the refractive index n clad In formula (1), n core represents the refractive index of the cured product of the core resin composition, and n clad represents the refractive index of the cured product of the cladding resin composition. Refractive index n core and the refractive index n clad The measurement wavelength is the wavelength of light transmitted through the optical waveguide, and is, for example, 1310 nm. The numerical aperture NA is, specifically, usually larger than 0.03, preferably larger than 0.04, particularly preferably larger than 0.05 or larger than 0.06. It is also usually less than 0.4, preferably 0.35 or less, more preferably 0.3 or less, particularly preferably 0.2 or less. The numerical aperture NA can be measured according to the method described in the Examples below.

number

[0120] The photosensitive resin composition set of the present invention can produce an optical waveguide having a small difference in shrinkage rate between the core layer and the clad layer. For example, the shrinkage rate S of the core layer core and the shrinkage rate S of the cladding layer clad Difference from |S core -S clad is preferably less than 0.05, more preferably 0.05 or less, further preferably 0.04 or less, 0.03 or less, 0.02 or less, or 0.01 or less. There is no particular lower limit, but it may be 0 or more, 0.0001 or more, etc. The difference in shrinkage rate can be measured according to the method described in the examples below.

[0121] The resin composition contains a combination of components (A) to (D), and therefore exhibits the property of excellent adhesion with a plated conductor layer. Specifically, after the resin composition is cured, the cured resin composition is subjected to a roughening treatment. The roughened surface is subjected to a copper plating treatment, and a conductor layer is formed on the cured resin composition to obtain a sample. The peel strength is measured using this sample. At this time, the peel strength is preferably 0.20 kgf / cm or more, more preferably 0.3 kgf / cm or more. There is no particular upper limit, but it may be 10 kgf / cm or less. The peel strength can be measured according to the method described in the examples below.

[0122] Since the resin composition contains a combination of the components (A) to (D), it usually exhibits the characteristic that dents after the desmear treatment are suppressed. Specifically, after the resin composition is cured, the cured resin composition is subjected to a roughening treatment, and the roughened surface is observed by SEM. At this time, no dents having a width of 2 μm or more and a depth of 1 μm or more are observed. The dents after the desmear treatment can be measured according to the method described in the examples below.

[0123] The resin composition contains a combination of the components (A) to (E), and therefore exhibits the characteristic of excellent developability (resolution). Therefore, it is possible to form an optical waveguide with excellent fine-line waveguide formability. For example, when attempting to form a line layer with a thickness of 5 μm and an L / S (line / space) of 5 μm / 5 μm, and a line layer with a thickness of 50 μm and an L / S (line / space) of 50 μm / 50 μm, it is preferable to form at least one of them, and particularly preferable to form both of them. The developability can be evaluated according to the method described in the examples below.

[0124] The resin composition contains a combination of the components (A) to (E), and therefore exhibits the characteristic of being able to reduce the optical transmission loss before a high temperature and high humidity environmental test (HAST test). Specifically, a test substrate having a cladding layer and a core layer formed using the photosensitive resin composition set is produced. The optical transmission loss is measured using this test substrate. At this time, the optical transmission loss (loss value) is preferably 0.7 dB / cm or less, more preferably 0.5 dB / cm or less, and even more preferably 0.4 dB / cm or less. The lower limit is not particularly limited, but may be 0 dB / cm or more, 0.01 dB / cm or more, etc. The optical transmission loss can be measured according to the method described in the examples below.

[0125] The resin composition contains a combination of the components (A) to (E), and therefore exhibits the property of being able to reduce optical transmission loss after a high temperature and high humidity environmental test (HAST test). Specifically, a test substrate having a cladding layer and a core layer formed using the photosensitive resin composition set is produced. The optical transmission loss after a high temperature storage test is measured using this test substrate. At this time, the optical transmission loss (loss value) is preferably 0.7 dB / cm or less, more preferably 0.6 dB / cm or less, and even more preferably 0.5 dB / cm or less. The lower limit is not particularly limited, but may be 0 dB / cm or more, 0.01 dB / cm or more, etc. The optical transmission loss can be measured according to the method described in the examples described below.

[0126] Since the resin composition contains a combination of the components (A) to (E), it usually exhibits the property of being able to reduce the rate of change in optical transmission loss before and after a high temperature and high humidity environmental test (HAST test). Specifically, a test substrate having a clad layer and a core layer formed using the photosensitive resin composition set is produced. The test substrate is used to measure the optical transmission loss before and after a high temperature storage test. At this time, the rate of change in optical transmission loss is preferably less than 30%, more preferably less than 20%, and even more preferably less than 15%. The lower limit is not particularly limited, but may be 0% or more, 0.1% or more, etc. The rate of change in optical transmission loss can be measured according to the method described in the examples below.

[0127] The photosensitive resin composition set of the present invention can reduce optical transmission loss, and therefore can be suitably used for forming an optical waveguide. Therefore, the photosensitive resin composition set of the present invention can be suitably used for forming an optical waveguide capable of transmitting light having a wavelength of 1300 nm to 1320 nm (photosensitive resin composition set for forming an optical waveguide capable of transmitting light having a wavelength of 1300 nm to 1320 nm). The photosensitive resin composition set of the present invention is preferably used for forming a single-mode optical waveguide, and is preferably used for forming a single-mode optical waveguide for light having a wavelength of 1310 nm, for example.

[0128] [Photosensitive resin sheet set] Photosensitive resin compositions such as the core resin composition and the clad resin composition may be used as a resin sheet. The resin sheet is a sheet having a resin composition layer containing the resin composition. Thus, from the core resin composition, a resin sheet having a resin composition layer containing the core resin composition (hereinafter, sometimes referred to as a "core resin sheet") is obtained. Also, from the clad resin composition, a resin sheet having a resin composition layer containing the clad resin composition (hereinafter, sometimes referred to as a "clad resin sheet") is obtained. Then, a photosensitive resin sheet set including the core resin sheet and the clad resin sheet can be obtained as a sheet set for manufacturing an optical waveguide. According to the photosensitive resin sheet set, the same advantages as those of the above-mentioned photosensitive resin composition set can be obtained, and further, since it is possible to manufacture an optical waveguide by a lamination method, it is possible to more easily manufacture an optical waveguide.

[0129] <Core resin sheet> The resin composition layer of the core resin sheet usually contains the core resin composition, and preferably contains only the core resin composition. The thickness of the resin composition layer of the core resin sheet can be set according to the thickness of the core layer. In terms of specific ranges, the thickness of the resin composition layer of the core resin sheet is preferably 0.5 μm or more, more preferably 1 μm or more, even more preferably 3 μm or more, and is preferably 100 μm or less, more preferably 50 μm or less, and particularly preferably 20 μm or less.

[0130] The core resin sheet may include a support. For example, the core resin sheet may include a support and a resin composition layer formed on the support. Examples of the support include a polyethylene terephthalate film, a polyethylene naphthalate film, a polypropylene film, a polyethylene film, a polyvinyl alcohol film, a triacetyl acetate film, and the like, and a polyethylene terephthalate film is particularly preferred.

[0131] Examples of commercially available supports include polyethylene terephthalate films such as those manufactured by Oji Paper Co., Ltd. under the product names "Alphan MA-410" and "E-200C," polypropylene films manufactured by Shin-Etsu Film Co., Ltd., and the PS series manufactured by Teijin Ltd. under the product name "PS-25." To facilitate peeling of the support after lamination, the surface of the support may be coated with a release agent such as an alkyd-based release agent or a silicone coating agent.

[0132] The thickness of the support is preferably in the range of 5 μm to 100 μm, and more preferably in the range of 10 μm to 50 μm.

[0133] In addition, in order to reduce scattering of light during exposure to actinic rays such as ultraviolet rays, the support is preferably one having excellent transparency. Specifically, the support is preferably one having a turbidity (haze standardized by JIS-K6714) as an index of transparency of 0.1 to 5. Furthermore, the photosensitive resin composition layer may be protected with a protective film.

[0134] The core resin sheet may be provided with a protective film for protecting the resin composition layer. Usually, the protective film is provided on the opposite side of the resin composition layer from the support. For example, a film formed of the same material as the support can be used as the protective film. The adhesive strength between the protective film and the resin composition layer is preferably smaller than the adhesive strength between the support and the resin composition layer. Usually, the core resin sheet is used after peeling off the protective film. It is preferable that the adhesive strength between the resin composition layer and the protective film is smaller than the adhesive strength between the resin composition layer and the support.

[0135] The core resin sheet can be manufactured, for example, by preparing a resin varnish by dissolving the core resin composition in an organic solvent, applying the resin varnish on a support, and drying the organic solvent by heating or blowing hot air to form a resin composition layer. Specifically, first, bubbles in the core resin composition are completely removed by a vacuum degassing method or the like, and then the core resin composition is applied on a support, the solvent is removed by a hot air oven or a far-infrared oven, and the resin composition layer is dried. Then, if necessary, a protective film is laminated on the obtained resin composition layer to manufacture a core resin sheet. Specific drying conditions vary depending on the curability of the core resin composition and the amount of organic solvent in the resin varnish, but in the case of a resin varnish containing 30% by mass to 60% by mass of organic solvent, drying can be performed at 80°C to 120°C for 3 minutes to 13 minutes. The amount of remaining organic solvent in the core resin composition layer is preferably 5% by mass or less, more preferably 2% by mass or less, based on the total amount of the resin composition layer, in order to prevent the diffusion of the organic solvent in the subsequent process. Those skilled in the art can determine suitable drying conditions through simple experiments.

[0136] Examples of methods for applying the core resin composition include gravure coating, microgravure coating, reverse coating, kiss reverse coating, die coating, slot die, lip coating, comma coating, blade coating, roll coating, knife coating, curtain coating, chamber gravure coating, slot orifice, spray coating, and dip coating.

[0137] The core resin composition may be applied in several portions, may be applied in one portion, or may be applied by a combination of different methods. Among them, the die coating method is preferable because of its excellent uniformity of application. In addition, in order to avoid contamination by foreign matter, it is preferable to carry out the application process in an environment where foreign matter is unlikely to be generated, such as a clean room.

[0138] <Resin sheet for clad> The resin composition layer of the clad resin sheet usually contains the clad resin composition, and preferably contains only the clad resin composition. The thickness of the resin composition layer of the clad resin sheet can be set according to the thickness of the clad layer. In terms of specific ranges, the thickness of the resin composition layer of the clad resin sheet is preferably 5 μm or more, more preferably 7 μm or more, even more preferably 10 μm or more, and is preferably 40 μm or less, more preferably 30 μm or less, and particularly preferably 20 μm or less.

[0139] The clad resin sheet may be the same as the core resin sheet, except that it has the above-mentioned resin composition layer containing the clad resin composition instead of the resin composition layer containing the core resin composition. Therefore, the clad resin sheet may have a support. The support of the clad resin sheet may be the same as the support of the core resin sheet. In addition, the clad resin sheet may have a protective film. The protective film of the clad resin sheet may be the same as the protective film of the core resin sheet. Usually, the clad resin sheet is used after peeling off the protective film.

[0140] The clad resin sheet can be produced in the same manner as the core resin sheet, except that the clad resin composition is used instead of the core resin composition.

[0141] The resin composition layer of the clad resin sheet may contain a solvent, but the amount of the solvent is preferably small. In one example, the amount of the solvent contained in the resin composition layer of the clad resin sheet may be in the same range as the amount of the solvent contained in the resin composition layer of the core resin sheet.

[0142] [Optical Waveguide and Manufacturing Method of Optical Waveguide] The above-mentioned photosensitive resin composition set and photosensitive resin sheet set can be used to manufacture an optical waveguide. Hereinafter, an embodiment of the optical waveguide will be described with reference to the drawings.

[0143] FIG. 1 is a perspective view showing a schematic diagram of an optical waveguide 10 according to one embodiment of the present invention. As shown in FIG. 1, the optical waveguide 10 includes a core layer 100 and a clad layer 200. The core layer 100 includes a cured product of the core resin composition of the present invention, and preferably includes only the cured product of the core resin composition of the present invention. The clad layer 200 includes a cured product of the clad resin composition of the present invention, and preferably includes only the cured product of the clad resin composition of the present invention. The cured product of the clad resin composition preferably has a lower refractive index than the cured product of the core resin composition.

[0144] The core layer 100 is provided in the clad layer 200. Thus, the core layer 100 is covered by the clad layer 200. Usually, the entire circumferential surface of the core layer 100 is covered by the clad layer 200. The core layer 100 and the clad layer 200 are in direct contact with each other without any other layer therebetween, and therefore, an interface 100I can be formed between the core layer 100 and the clad layer 200. Usually, the core layer 100 has a higher refractive index than the clad layer 200, and therefore, light (not shown) can be transmitted through the core layer 100 from one end (the end on the incident side) 100A of the core layer 100 to the other end (the end on the exit side) 100B.

[0145] The wavelength of light that can be transmitted by the optical waveguide 10 can be selected from various wavelengths. For example, the preferred wavelength range of the transmitted light can be 840 nm to 860 nm (e.g., 850 nm), 1300 nm to 1320 nm (e.g., 1310 nm), 1540 nm to 1560 nm (e.g., 1550 nm), etc. Among them, the preferred wavelength range of the light transmitted through the optical transmission line 10 is 1300 nm to 1320 nm.

[0146] The optical waveguide 10 may be a single-mode optical waveguide or a multimode optical waveguide, but is preferably a single-mode optical waveguide. In particular, the optical waveguide 10 is preferably a single-mode optical waveguide for light in the above-mentioned preferred wavelength range. For example, the optical waveguide 10 is preferably a single-mode optical waveguide for light of 1310 nm.

[0147] It is desirable to set the width L of the core layer 100 appropriately within a range in which light transmission is possible. A specific range of the line width L of the core layer 100 is preferably 0.5 μm or more, more preferably 1 μm or more, particularly preferably 2 μm or more, and is preferably 50 μm or less, more preferably 30 μm or less, particularly preferably 20 μm or less, and may be 10 μm or less or 5 μm or less. The width L of the core layer 100 corresponds to the line width (line) of the core layer 100 when viewed in the thickness direction.

[0148] It is desirable to set the interval S of the core layers 100 appropriately within a range in which light transmission is possible. A specific range of the interval S of the core layers 100 is preferably 50 μm or more, more preferably 70 μm or more, particularly preferably 100 μm or more, and preferably 1000 μm or less, more preferably 500 μm or less, particularly preferably 300 μm or less. The interval S of the core layers 100 corresponds to the interval (space) of the core layers as viewed in the thickness direction.

[0149] It is desirable to appropriately set the thickness T of the core layer 100 within a range in which light transmission is possible. A specific range of the thickness T of the core layer 100 is preferably 0.5 μm or more, more preferably 1 μm or more, particularly preferably 2 μm or more, and is preferably 50 μm or less, more preferably 30 μm or less, particularly preferably 20 μm or less, and may be 10 μm or less.

[0150] The thickness of the cladding layer 200 is usually greater than the thickness of the core layer 100. The specific thickness of the cladding layer 200 is preferably 5 μm or more, more preferably 7 μm or more, particularly preferably 10 μm or more, and is preferably 40 μm or less, more preferably 30 μm or less, particularly preferably 20 μm or less.

[0151] The optical waveguide 10 may include any element other than the core layer 100 and the clad layer 200, as necessary. For example, the optical waveguide 10 may include a conductor layer (not shown) made of plating or the like on the core layer, and a substrate 300. In the optical waveguide 10 including the substrate 300, the clad layer 200 is usually provided on the substrate 300, and the core layer 100 is provided within the clad layer 200.

[0152] The substrate 300 may be a hard substrate such as a glass substrate, a metal substrate, a ceramic substrate, a wafer, or a circuit substrate. The wafer may be a semiconductor wafer such as a silicon wafer, a gallium arsenide (GaAs) wafer, an indium phosphide (InP) wafer, a gallium phosphide (GaP) wafer, a gallium nitride (GaN) wafer, a gallium telluride (GaTe) wafer, a zinc selenium (ZnSe) wafer, or a silicon carbide (SiC) wafer, or a pseudo wafer. The pseudo wafer may be a plate-shaped member having a mold resin and electronic components embedded in the mold resin. The circuit substrate may be a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, or a thermosetting polyphenylene ether substrate. The circuit substrate may be a substrate having a patterned conductor layer (circuit) formed on one or both sides of the substrate. The substrate 300 may be a film formed of a plastic material such as polyethylene terephthalate, polyimide, or polyester. Furthermore, a flexible circuit board may be employed as the substrate 300 .

[0153] Furthermore, the optical waveguide 10 may include, as an optional element, a protective layer (not shown) for protecting the core layer 100 and the cladding layer 200. The protective layer may be provided, for example, so as to cover the surface of the cladding layer 200 opposite to the substrate 300.

[0154] As described above, the optical waveguide 10 can have a small transmission loss. In addition, since the optical waveguide 10 can be formed using a core resin composition and a clad resin composition that have excellent core formability and can suppress the occurrence of surface irregularities, the core layer can be finely wired, and the optical waveguide 10 can be formed with a small line width L as described above.

[0155] The optical waveguide 10 can be produced using either the photosensitive resin composition set of the present invention or the photosensitive resin sheet set of the present invention. For example, the optical waveguide 10 can be produced using A step (I) of forming a first composition layer containing a cladding resin composition; A step (II) of curing the first composition layer; (III) forming a second composition layer containing a core resin composition on the first composition layer; A step (IV) of subjecting the second composition layer to an exposure treatment; A step (V) of subjecting the second composition layer to a development treatment; A step (VI) of curing the second composition layer; (VII) forming a third composition layer containing a cladding resin composition on the second composition layer; A step (VIII) of curing the third composition layer; In addition, if necessary, the method may further include a step (IX) of forming a conductor layer on the cladding layer after the step (VIII).

[0156] Fig. 2 is a schematic cross-sectional view for explaining step (I) of the method for producing an optical waveguide according to one embodiment of the present invention. As shown in Fig. 2, the method for producing an optical waveguide according to one embodiment of the present invention includes step (I) of forming a first composition layer 210 containing a cladding resin composition. In this embodiment, an example of forming the first composition layer 210 on a substrate 300 will be shown and explained.

[0157] There is no particular limitation on the method for forming the first composition layer 210. For example, the first composition layer 210 may be formed by applying a clad resin composition onto the substrate 300. From the viewpoint of smooth application, a varnish-like clad resin composition containing a solvent may be prepared, and the varnish-like clad resin composition may be applied.

[0158] Examples of coating methods include gravure coating, microgravure coating, reverse coating, kiss reverse coating, die coating, slot die, lip coating, comma coating, blade coating, roll coating, knife coating, curtain coating, chamber gravure coating, slot orifice, spin coating, slit coating, spray coating, dip coating, hot melt coating, bar coating, applicator, air knife coating, curtain flow coating, offset printing, brush coating, and screen printing.

[0159] The cladding resin composition may be applied in one application or in multiple applications. Also, different application methods may be combined. In order to avoid contamination by foreign matter, it is preferable to apply the composition in an environment where foreign matter is unlikely to be generated, such as a clean room.

[0160] After application of the cladding resin composition, the first composition layer 210 may be dried as necessary. Drying can be performed using a drying device such as a hot air oven or a far infrared oven. It is preferable to set the drying conditions appropriately according to the composition of the cladding resin composition. To give a specific example, the drying temperature is preferably 50° C. or higher, more preferably 70° C. or higher, particularly preferably 80° C. or higher, and preferably 150° C. or lower, more preferably 130° C. or lower, particularly preferably 120° C. or lower. The drying time is preferably 30 seconds or higher, more preferably 60 seconds or higher, particularly preferably 120 seconds or higher, and preferably 60 minutes or less, more preferably 20 minutes or less, particularly preferably 5 minutes or less.

[0161] The first composition layer 210 may be formed, for example, by using a clad resin sheet including a support and a resin composition layer made of a clad resin composition. As a specific example, the first composition layer 210 can be formed on the substrate 300 by laminating the clad resin composition layer of the clad resin sheet onto the substrate 300. The lamination is usually performed by pressing the clad resin composition layer of the resin sheet onto the substrate 300 while heating it. This lamination is preferably performed under reduced pressure by a vacuum lamination method. Furthermore, prior to lamination, a preheat treatment may be performed to heat the resin sheet and the substrate, if necessary.

[0162] The lamination conditions are, for example, a pressure bonding temperature (lamination temperature) of 70°C to 140°C and a pressure bonding pressure of 1kgf / cm. 2 ~11kgf / cm 2 (9.8×10 4 N / m 2 ~107.9×10 4 N / m 2 ) and a pressure bonding time of 5 to 300 seconds. The lamination is preferably carried out under reduced pressure with an air pressure of 20 mmHg (26.7 hPa) or less. The lamination may be carried out in a batch manner or continuously using a roll.

[0163] The vacuum lamination method can be performed using a commercially available vacuum laminator, such as a vacuum applicator manufactured by Nikko Materials Co., Ltd., a vacuum pressure laminator manufactured by Meiki Seisakusho Co., Ltd., a roll-type dry coater manufactured by Hitachi Industries Co., Ltd., and a vacuum laminator manufactured by Hitachi AIC Co., Ltd.

[0164] When the first composition layer 210 is formed using a clad resin sheet having a support, the support is usually peeled off at an appropriate time before the step (III).

[0165] The first composition layer 210 formed on the substrate 300 in step (I) usually contains a cladding resin composition, and preferably contains only a cladding resin composition.

[0166] The method for producing an optical waveguide according to one embodiment of the present invention includes, after step (I), step (II) of curing the first composition layer 210. This step (II) may, for example, involve heat treating the first composition layer 210. The conditions for the heat treatment may be selected depending on the type and amount of the resin component in the cladding resin composition, and may be preferably in the range of 150°C to 250°C for 20 minutes to 180 minutes, and more preferably in the range of 160°C to 230°C for 30 minutes to 120 minutes. The heat treatment is preferably carried out in an inert atmosphere such as a nitrogen atmosphere.

[0167] The first composition layer 210 may be cured by exposure to light. In one example, the specific exposure dose range is preferably 10 mJ / cm. 2 More preferably, 50 mJ / cm 2 More than 200 mJ / cm 2 or more, preferably 10,000 mJ / cm 2 Less than or equal to 8,000 mJ / cm 2 Less than 4,000 mJ / cm, more preferably 4,000 mJ / cm 2 Below 1,000 mJ / cm, particularly preferably 2 The first composition layer 210 may also be cured by a combination of an exposure treatment and a heat treatment.

[0168] Fig. 3 is a schematic cross-sectional view for explaining step (II) of the method for producing an optical waveguide according to one embodiment of the present invention. By curing the first composition layer 210 in step (II), a cured first composition layer 220 is obtained on the substrate 300, as shown in Fig. 3. This cured first composition layer 220 forms a part of the cladding layer 200, and may be referred to as the "lower cladding layer" 220 hereinafter.

[0169] 4 is a schematic cross-sectional view for explaining step (III) of the method for producing an optical waveguide according to one embodiment of the present invention. The method for producing an optical waveguide according to one embodiment of the present invention includes, after step (II), step (III) of forming a second composition layer 110 containing a core resin composition on a lower clad layer 220 as a cured first composition layer, as shown in FIG.

[0170] There is no particular limitation on the method for forming the second composition layer 110. For example, the second composition layer 110 may be formed by applying a core resin composition onto the lower clad layer 220. From the viewpoint of smooth application, a varnish-like core resin composition containing a solvent may be prepared, and the varnish-like core resin composition may be applied. The application of the core resin composition may be performed in the same manner as the application of the clad resin composition. After application of the core resin composition, the second composition layer 110 may be dried as necessary. The drying of the second composition layer 110 may be performed using the same method and conditions as those for drying the first composition layer 210.

[0171] The second composition layer 110 may be formed, for example, by using a core resin sheet. As a specific example, the resin composition layer of the core resin sheet is laminated onto the lower clad layer 220, thereby forming the second composition layer 110 on the lower clad layer 220. The lamination of the core resin sheet can be performed in the same manner as the lamination of the clad resin sheet. In addition, the support of the core resin sheet is peeled off at an appropriate time before the step (V).

[0172] The second composition layer 110 formed on the lower clad layer 220 in the step (III) usually contains a core resin composition, and preferably contains only a core resin composition.

[0173] 5 is a schematic cross-sectional view for explaining step (IV) of the method for producing an optical waveguide according to one embodiment of the present invention. As shown in FIG. 5, the method for producing an optical waveguide according to one embodiment of the present invention includes, after step (III), step (IV) of subjecting the second composition layer 110 to an exposure treatment.

[0174] In step (V), a latent image is formed in the second composition layer 110 by exposure treatment. Specifically, in the exposure treatment, light P is selectively irradiated to a specific portion of the second composition layer 110. Thus, when the exposure treatment is performed, the second composition layer 110 is provided with an exposed portion 111 that is irradiated with light and a non-exposed portion 112 that is not irradiated with light. Usually, the core resin composition functions as a negative photosensitive resin composition, so that the exposed portion 111 forms a latent image corresponding to the core layer.

[0175] From the viewpoint of performing selective exposure, the exposure treatment in the step (V) is usually performed using a mask 400. Specifically, in this exposure treatment, the second composition layer 110 is irradiated with light P through the mask 400 having a light-transmitting portion 410 and a light-shielding portion 420. The light P passes through the light-transmitting portion 410 and enters the exposed portion 111, but cannot pass through the light-shielding portion 420 and therefore cannot enter the non-exposed portion 112. Therefore, the exposed portion 111 and the non-exposed portion 112 corresponding to the light-transmitting portion 410 and the light-shielding portion 420 can be provided in the second composition layer 110. The mask 400 may be brought into close contact with the second composition layer 110 as shown in FIG. 5 (contact exposure method), or exposure may be performed using parallel light without being in close contact (non-contact exposure method).

[0176] In general, the light-transmitting portion 410 of the mask 400 is formed to have a planar shape corresponding to the core layer of the optical waveguide. Therefore, the light-shielding portion 420 of the mask 400 is formed to have a planar shape corresponding to the portion of the optical waveguide where the core layer is not present. Unless otherwise specified, the "planar shape" refers to the shape seen from the thickness direction. The light-transmitting portion 410 formed in the planar shape corresponding to the core layer may be referred to as a "mask pattern" hereinafter.

[0177] As the light P used in the exposure treatment in step (V), it is preferable to use an appropriate actinic ray according to the composition of the core resin composition. The wavelength of the actinic ray is usually 190 nm to 1000 nm, preferably 240 nm to 550 nm, but light rays with other wavelengths may also be used. Specific examples of the actinic light source include ultraviolet light, visible light, electron beams, X-rays, etc., and ultraviolet light is particularly preferable. The exposure dose of the light P is preferably set so that a desired core layer can be formed after curing in step (VII). In one example, the specific range of the exposure dose in step (V) is preferably 10 mJ / cm. 2 More preferably, 50 mJ / cm 2 More than 200 mJ / cm 2 or more, preferably 10,000 mJ / cm 2 Less than or equal to 8,000 mJ / cm 2 Less than 4,000 mJ / cm, more preferably 4,000 mJ / cm 2 Below 1,000 mJ / cm, particularly preferably 2 The following is the result.

[0178] When the second composition layer 110 is formed using the resin sheet of the present invention, in step (IV), a support (not shown) may be present on the second composition layer 110. When a support is present on the second composition layer 110, exposure may be performed through the support, or exposure may be performed after peeling off the support.

[0179] The core resin composition usually functions as a negative photosensitive resin composition, and therefore has low solubility in a developer in the exposed area 111. On the other hand, the non-exposed area 112 has high solubility in a developer. Utilizing the difference in solubility between the exposed area 111 and the non-exposed area 112, the subsequent development process in step (VI) is carried out.

[0180] The method for producing an optical waveguide according to one embodiment of the present invention may include a step (IV-2) of heating the second composition layer 110 after the step (IV) and before the step (V) in order to harden the second composition layer 110. The step (IV-2) can quickly reduce the solubility of the exposed portion 111 in a developer. The heating in the step (IV-2) may be performed using a hot plate or an oven. The heating temperature may be, for example, 40° C. or more and 110° C. or less. The heating time may be, for example, 30 seconds or more and 60 minutes or less.

[0181] FIG. 6 is a schematic cross-sectional view for explaining step (V) of the method for producing an optical waveguide according to one embodiment of the present invention. The method for producing an optical waveguide according to one embodiment of the present invention includes step (V) of subjecting the second composition layer 110 to a development treatment after step (IV). The development treatment allows the latent image formed in step (IV) to be developed. Since the core resin composition usually functions as a negative photosensitive resin composition, as shown in FIG. 6, the exposed portion 111 is not removed by the development treatment, while the non-exposed portion 112 (see FIG. 5) is removed. The exposed portion 111 of the second composition layer 110 remaining after development may have the same planar shape as the mask pattern of the light-transmitting portion 410 (see FIG. 5) of the mask 400 used in step (IV).

[0182] The developing method is usually a wet developing method in which the second composition layer 110 is brought into contact with a developer. An alkaline aqueous solution is usually used as the developer.

[0183] Examples of the alkaline aqueous solution as a developer include an aqueous solution of an alkali metal compound. Examples of the alkali metal compound include alkali metal hydroxides such as lithium hydroxide, sodium hydroxide, and potassium hydroxide; alkali metal carbonates or bicarbonates such as sodium carbonate and sodium bicarbonate; alkali metal phosphates such as sodium phosphate and potassium phosphate; and alkali metal pyrophosphates such as sodium pyrophosphate and potassium pyrophosphate. Examples of the alkaline aqueous solution include an aqueous solution of an organic base that does not contain metal ions, such as tetraalkylammonium hydroxide. The alkaline aqueous solution may be used alone or in combination of two or more. Among them, from the viewpoint of obtaining the effects of the present invention remarkably, an alkali metal carbonate or bicarbonate is preferable, and sodium carbonate is more preferable.

[0184] The developer may contain additives such as a surfactant and an antifoaming agent, if necessary, to improve the developing action.

[0185] The development time is preferably 10 seconds to 5 minutes. The temperature of the developer during development is not particularly limited, but is preferably 20° C. or higher and preferably 50° C. or lower, more preferably 40° C. or lower.

[0186] Examples of the developing method include a paddle method, a spray method, an immersion method, a brushing method, a slapping method, and an ultrasonic method. Among them, the spray method is suitable for improving the resolution. When the spray method is adopted, the spray pressure is preferably 0.05 MPa to 0.3 MPa.

[0187] After development using the developer, the second composition layer 110 may be further rinsed. Rinsing is preferably performed with a solvent different from the developer. For example, rinsing may be performed with the same type of solvent contained in the core resin composition or water. The rinsing time is preferably 5 seconds to 1 minute.

[0188] In addition, after development using a developer, a desmear treatment may be performed to remove non-exposed areas that cannot be completely removed by development. The desmear treatment may be performed according to various methods used in the manufacture of printed wiring boards and known to those skilled in the art.

[0189] The method for producing an optical waveguide according to one embodiment of the present invention includes, after step (V), step (VI) of curing the second composition layer 110. This step (VI) usually includes heat treating the second composition layer 110. The conditions for the heat treatment may be selected depending on the type and amount of the resin component in the core resin composition. For example, the conditions for the heat treatment in step (VI) may be the same as the conditions for the heat treatment of the first composition layer 210 in step (II).

[0190] 7 is a schematic cross-sectional view for explaining step (VI) of the method for producing an optical waveguide according to one embodiment of the present invention. By curing second composition layer 110 in step (VI), as shown in FIG. 7, core layer 100 is obtained as a cured second composition layer on lower clad layer 220.

[0191] 8 is a schematic cross-sectional view for explaining step (VII) of the method for producing an optical waveguide according to one embodiment of the present invention. As shown in FIG. 8, the method for producing an optical waveguide according to one embodiment of the present invention includes, after step (VI), step (VII) of forming a third composition layer 230 containing a cladding resin composition on the core layer 100. The third composition layer 230 is usually formed so as to cover the entire surface of the core layer 100 that is not in contact with the lower cladding layer 220. Thus, the third composition layer 230 is formed so as to cover the core layer 100 and is also formed on the lower cladding layer 220.

[0192] There is no particular limitation on the method for forming the third composition layer 230. For example, the third composition layer 230 may be formed by applying a clad resin composition onto the core layer 100 (and, if necessary, onto the lower clad layer 220). The application of the clad resin composition for forming the third composition layer 230 may be performed in the same manner as the application of the clad resin composition for forming the first composition layer 210. Furthermore, after application of the clad resin composition, the third composition layer 230 may be dried, if necessary. The third composition layer 230 may be dried using the same method and conditions as those for drying the first composition layer 210.

[0193] The third composition layer 230 may be formed, for example, using a clad resin sheet. As a specific example, the photosensitive resin composition layer of the clad resin sheet is laminated to the core layer 100 (and the lower clad layer 220, if necessary), thereby forming the third composition layer 230 on the core layer 100. The lamination of the clad resin sheet for forming the third composition layer 230 may be performed in the same manner as the lamination of the clad resin sheet for forming the first composition layer 210. When the third composition layer 230 is formed using a clad resin sheet provided with a support, the support may be peeled off in any step.

[0194] The third composition layer 230 formed on the core layer 100 in step (VII) usually contains a cladding resin composition, and preferably contains only a cladding resin composition.

[0195] The method for producing an optical waveguide according to one embodiment of the present invention includes, after the step (VII), a step (VIII) of curing the third composition layer 230. The effect of the third resin composition layer 230 in this step (VIII) can usually be achieved in the same manner as the curing of the first composition layer 210.

[0196] 9 is a schematic cross-sectional view for explaining step (VIII) of the method for producing an optical waveguide according to one embodiment of the present invention. By curing the third composition layer 230 in step (VIII), a cured third composition layer 240 is obtained on the core layer 100 as shown in FIG. This cured third composition layer 240 forms a part of the cladding layer 200, and may be referred to as the "upper cladding layer" 240 hereinafter. The upper cladding layer 240 and the lower cladding layer 220 form the cladding layer 200. Thus, an optical waveguide 10 including the cladding layer 200 including the lower cladding layer 220 and the upper cladding layer 240, and the core layer 100 provided in the cladding layer 200 can be obtained.

[0197] FIG. 10 is a schematic cross-sectional view for explaining step (IX) of the method for producing an optical waveguide according to one embodiment of the present invention. The method for producing an optical waveguide according to one embodiment of the present invention may include step (IX) of forming a conductor layer on the clad layer after step (VIII). The conductor layer 500 formed on the upper clad layer 240 is preferably formed by plating. Furthermore, before forming the conductor layer 500 by plating, the surface of the upper clad layer 240 may be roughened. Since the upper clad layer 240 contains the resin composition for clad of the present invention, it is possible to improve the peel strength between the core layer 100 and the conductor layer 500 even if the arithmetic mean roughness (Ra) after the roughening treatment is small.

[0198] The procedure and conditions of the roughening treatment are not particularly limited. For example, the insulating layer can be roughened by carrying out a swelling treatment with a swelling liquid, a roughening treatment with an oxidizing agent, and a neutralization treatment with a neutralizing liquid in this order.

[0199] Examples of the swelling liquid used in the roughening treatment include an alkaline solution and a surfactant solution, and an alkaline solution is preferred. As the alkaline solution, a sodium hydroxide solution and a potassium hydroxide solution are more preferred. Examples of commercially available swelling liquids include "Swelling Dip Securigans P" and "Swelling Dip Securigans SBU" manufactured by Atotech Japan. The swelling treatment using the swelling liquid is not particularly limited, but can be performed by immersing the insulating layer in a swelling liquid at 30°C to 90°C for 1 to 20 minutes. From the viewpoint of suppressing the swelling of the resin of the insulating layer to an appropriate level, it is preferred to immerse the insulating layer in a swelling liquid at 40°C to 80°C for 5 to 15 minutes.

[0200] An example of an oxidizing agent used in the roughening treatment is an alkaline permanganate solution in which potassium permanganate or sodium permanganate is dissolved in an aqueous solution of sodium hydroxide. The roughening treatment using an oxidizing agent such as an alkaline permanganate solution is preferably performed by immersing the insulating layer in an oxidizing agent solution heated to 60°C to 100°C for 10 minutes to 30 minutes. The concentration of permanganate in the alkaline permanganate solution is preferably 5% by mass to 10% by mass. Examples of commercially available oxidizing agents include alkaline permanganate solutions such as "Concentrate Compact CP" and "Dosing Solution Securigans P" manufactured by Atotech Japan.

[0201] The neutralizing solution used in the roughening treatment is preferably an acidic aqueous solution, and a commercially available product is, for example, "Reduction Solution Securigant P" manufactured by Atotech Japan. Treatment with a neutralizing solution can be performed by immersing the surface that has been roughened with an oxidizing agent in a neutralizing solution at 30°C to 80°C for 5 to 30 minutes. From the viewpoint of workability, etc., a method in which the object that has been roughened with an oxidizing agent is immersed in a neutralizing solution at 40°C to 70°C for 5 to 20 minutes is preferred.

[0202] The arithmetic mean roughness Ra of the upper clad layer surface after the roughening treatment is preferably 500 nm or less, more preferably less than 400 nm, even more preferably 200 nm or less, more preferably less than 200 nm. There is no particular lower limit, and it can be, for example, 1 nm or more, 2 nm or more, etc.

[0203] After completion of the roughening treatment, the conductor layer 500 is formed on the upper clad layer 240 that has been subjected to the roughening treatment. Specifically, the surface of the core layer 100 is plated by a method such as a semi-additive method or a full-additive method to form the conductor layer 500 having a desired wiring pattern. From the viewpoint of ease of production, it is preferable to form the conductor layer by the semi-additive method. An example of forming the conductor layer by the semi-additive method will be described below.

[0204] A plating seed layer is formed on the surface of the upper cladding layer 240 by electroless plating. Next, a mask pattern is formed on the formed plating seed layer to expose a part of the plating seed layer corresponding to the desired wiring pattern. After a metal layer is formed on the exposed plating seed layer by electrolytic plating, the mask pattern is removed. Thereafter, unnecessary plating seed layer is removed by etching or the like to form a conductor layer 500 having a desired wiring pattern.

[0205] The method for producing the optical waveguide 10 may further include any optional steps in combination with the steps described above.

[0206] The method for manufacturing the optical waveguide 10 may include, for example, a step of forming a protective layer (not shown). The method for manufacturing the optical waveguide 10 may also include, for example, a step of dicing the manufactured optical waveguide 10.

[0207] The above-mentioned steps may be repeated in the method for producing the optical waveguide 10. For example, steps (I) to (IX) may be repeated to produce an optical waveguide having a multilayer structure in which core layers and clad layers are alternately provided on the substrate 300 in the thickness direction.

[0208] [Opto-electrical hybrid board and its manufacturing method] An optical / electrical hybrid board according to an embodiment of the present invention includes the optical waveguide described above. Typically, the optical / electrical hybrid board includes an optical waveguide and an electric circuit board. The electric circuit board may include electronic components and wiring connected to the electronic components. Examples of the electronic components include passive components such as capacitors, inductors, and resistors; active components such as semiconductor chips; and the like. The optical waveguide and the wiring of the electric circuit board may be connected via a photoelectric conversion element. The photoelectric conversion element may include a combination of a light-emitting element (e.g., a surface-emitting light-emitting diode) capable of converting electricity into light, and a light-receiving element (e.g., a photodiode) capable of converting light into electricity. Furthermore, the optical / electrical hybrid board may include an optical element such as a mirror for adjusting the optical path.

[0209] A preferred example of an opto-electrical hybrid board is one that includes a chip in which an optical integrated circuit is formed on a silicon wafer. This chip is expected to be put to practical use in the near future using silicon photonics, and is expected to be mounted, for example, in a semiconductor package. An opto-electrical hybrid board that includes this chip includes, for example, an electric circuit board, a chip mounted on the electric circuit board, and an optical waveguide. The optical waveguide can be used to connect the wiring of the electric circuit board to the chip, or to connect multiple chips together.

[0210] In chips manufactured by silicon photonics, generally, light with wavelengths of 1310 nm and 1550 nm is often used, with 1310 nm being the most common (Sho Yoshida, Daisuke Suganuma, Takaaki Ishigure, "Fabrication of Single-Mode Polymer Waveguides and Low Loss Using the Mosquito Method," 28th Spring Lecture Meeting of the Japan Institute of Electronics Packaging, 2014). Therefore, it is preferable that the optical waveguide is capable of transmitting light with wavelengths of 1310 nm and 1550 nm or close thereto, and for example, it is preferable that the optical waveguide is capable of transmitting light with wavelengths of 1300 nm to 1320 nm. The optical waveguide according to the above-mentioned embodiment is capable of transmitting light with these wavelengths.

[0211] Generally, the single mode can achieve faster transmission than the multimode. Therefore, from the viewpoint of high-speed transmission, the single mode optical waveguide is preferable as an optical waveguide applied to an optical-electrical hybrid circuit. In the single mode optical waveguide, the width of the core layer is preferably small. For example, it is preferable to form a core layer having a width of 10 μm or less, or 5 μm or less. In addition, an optical waveguide having such a small core layer is preferable from the viewpoint of increasing the degree of freedom in package design when the optical waveguide is applied to a semiconductor package. According to the optical waveguide according to the above-mentioned embodiment, it is possible to reduce the width of the core layer as described above.

[0212] On the other hand, when connecting multiple opto-electric hybrid boards, the boards may be connected via optical fibers. For example, multiple opto-electric hybrid boards may be installed in a rack, and the opto-electric hybrid boards may be connected to each other via optical fibers. Multimode optical fibers are the mainstream for connecting boards in this way. Therefore, from the viewpoint of enabling connection with the optical fibers, a multimode optical waveguide may be adopted as the optical waveguide provided in the opto-electric hybrid board.

[0213] From the viewpoint of increasing versatility, it is desirable that the optical waveguide is applicable to both single mode and multimode. Furthermore, it is desirable to reduce the minimum width of the core layer of the optical waveguide to increase the degree of freedom of the line width of the core layer. According to the optical waveguide of the above-mentioned embodiment, by using the core resin composition, a fine core can be formed and the occurrence of surface unevenness of the core can be suppressed, so that the minimum width of the core layer can be reduced. Furthermore, according to the optical waveguide of the above-mentioned embodiment, both single mode and multimode optical waveguides can be obtained. Therefore, the optical waveguide of the above-mentioned embodiment can be applied in a wide range. And, since it is applicable in such a wide range and can suppress the transmission loss of light, the optical waveguide of the above-mentioned embodiment is suitable for application to an opto-electrical hybrid board.

[0214] Since the opto-electrical hybrid board includes the above-mentioned optical waveguide, the manufacturing method of the opto-electrical hybrid board includes the same method as the manufacturing method of the optical waveguide. EXAMPLES

[0215] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. In the following description, "parts" and "%" representing amounts mean "parts by mass" and "% by mass", respectively, unless otherwise specified. Furthermore, the operations described below were carried out in the atmosphere at room temperature and normal pressure (23°C and 1 atm), unless otherwise specified.

[0216] <Synthesis Example 1: Synthesis of resin containing carboxyl groups> 325 parts of an epoxy resin having a naphthol aralkyl skeleton with an epoxy equivalent of 330 g / eq. ("ESN-475V", manufactured by Nippon Steel Chemical & Material Co., Ltd.) was placed in a flask equipped with a gas inlet tube, a stirrer, a cooling tube, and a thermometer, 340 parts of propylene glycol monomethyl ether was added, and the mixture was dissolved by heating, and 0.46 parts of hydroquinone and 1 part of triphenylphosphine were added. The mixture was heated to 95 to 105°C, and 72 parts of acrylic acid were gradually added dropwise and reacted for 16 hours. The reaction product was cooled to 80 to 90°C, and 130 parts of tetrahydrophthalic anhydride was added, reacted for 8 hours, and cooled. The solvent was removed to obtain an acid-modified epoxy acrylate resin having an acid value of 90 mgKOH / g and a solid content of 70 mass%. The weight average molecular weight was 1000.

[0217] <Production Example 1: Production of Core Resin Composition> The mixture was mixed with 21.5 parts of the carboxyl group-containing resin obtained in Synthesis Example 1, 10 parts of a naphthol aralkyl skeleton epoxy resin ("ESN-475V" manufactured by Nippon Steel Chemical & Material Co., Ltd., epoxy equivalent: about 330 g / eq.), 5 parts of a naphthalene-type tetrafunctional epoxy resin ("HP-4710" manufactured by DIC Corporation, epoxy equivalent: 170 g / eq.), 12.5 parts of a photoreactive resin ("DPHA" manufactured by Nippon Kayaku Co., Ltd., dipentaerythritol hexaacrylate), and 12.5 parts of a photopolymerization initiator ("Omnirad" manufactured by IGM). A varnish-like core resin composition was prepared by mixing 1.5 parts of a curing accelerator (2-phenyl-1-benzyl-1H-imidazole, manufactured by Shikoku Kasei Corporation), 0.2 parts of a high molecular weight component (polyfunctional carboxyl group-containing acrylic polymer (CB-3060, manufactured by Soken Chemical & Engineering Co., Ltd., 2EHA skeleton, weight average molecular weight 3000, acid value 60 mgKOH / g, Tg: -70°C)), 15 parts of methyl ethyl ketone, and 1.5 parts of propylene glycol monomethyl ether using a high-speed rotating mixer.

[0218] <Production Examples 2 to 14: Production of Core and Clad Resin Compositions> Core or clad resin compositions were produced in the same manner as in Production Example 1, except that the components were mixed according to the composition shown in the table below. In the table, the amount of each component means parts by mass, and indicates the actual amount used. Production Examples 1 and 9 are core resin compositions, and Production Examples 2 to 8 and Production Examples 10 to 14 are clad resin compositions.

[0219] [Table 1]

[0220] The abbreviations in the table are as follows: Component (A) CB-3060: Multifunctional carboxyl group-containing acrylic polymer (Soken Chemical Industries, 2EHA skeleton, weight average molecular weight 3000, acid value 60mgKOH / g, Tg: -70℃) CB-3098: Multifunctional carboxyl group-containing acrylic polymer (Soken Chemical Industries, Ltd., 2EHA skeleton, weight average molecular weight 3000, acid value 98 mgKOH / g, Tg: -70°C) UT-1001: Hydroxyl-containing acrylic polymer (Soken Chemical Industries, 2EHA skeleton, weight average molecular weight 3000, hydroxyl value 57 mgKOH / g, Tg: -70°C) AB-6: Polybutyl acrylate containing a methacryloyl group at one end (manufactured by Toagosei Co., Ltd., weight average molecular weight 13,000, Tg: -55°C) UE-3980: Polyester (Unitika, weight average molecular weight 8000, Tg: 58℃) (B) Component Synthesis Example 1: Resin containing carboxyl groups synthesized in Synthesis Example 1 (C) Component HP-4710: Naphthalene-type tetrafunctional epoxy resin (DIC "HP-4710", epoxy equivalent 170g / eq.) ESN-475V: Naphthol aralkyl-based epoxy resin ("ESN-475V" manufactured by Nippon Steel Chemical & Material Co., Ltd., epoxy equivalent: approx. 330g / eq.) (D) Component DPHA: Dipentaerythritol hexaacrylate (Nippon Kayaku Co., Ltd., acrylic equivalent: approx. 96 g / eq.) (E) Component Omnirad 379EG: A compound represented by the following structure (manufactured by IGM, molecular weight 380.5, 2-dimethylamino-2-(4-methyl-benzyl)-1-(4-morpholin-4-yl-phenyl)-butan-1-one, CAS 119344-86-4) [ka] Ingredient (F) 1B2PZ: 2-phenyl-1-benzyl-1H-imidazole, manufactured by Shikoku Kasei Co., Ltd. (H) Component US-1071: Carboxyl group-containing acrylic polymer (Seiko PMC, weight average molecular weight 9500, acid value 75 mgKOH / g, Tg: 104°C) UE-3410: Rubber-like polyester (Unitika, weight average molecular weight 23000, Tg: -32℃)

[0221] <Preparation of Core and Clad Resin Sheets> A polyethylene terephthalate film (Toray Industries, Inc., "Lumirror T6AM", thickness 38 μm, softening point 130° C.) was prepared as a support. The varnish-like resin composition prepared above was uniformly applied to the support with a die coater so that the thickness of the resin composition layer after drying was 5 μm, 6.5 μm, 10 μm, 20 μm, and 50 μm, and the resin composition layer was formed by drying at 80° C. to 110° C. (maximum temperature 110° C.) for 7 minutes. Next, a protective film (biaxially oriented polypropylene film, Oji F-Tex Co., Ltd., "MA-411") was placed on the surface of the resin composition layer and laminated at 80° C. to produce a resin sheet having a three-layer structure of support / resin composition layer / protective film.

[0222] <Measurement of refractive index of cured resin composition> The protective film was peeled off from the resin sheet having a 6.5 μm-thick resin composition layer. The resin sheet was then laminated on a silicon wafer at 80° C., and the support was peeled off to form a 6.5 μm-thick resin composition layer on the silicon wafer. Thereafter, the resin composition layer was exposed to light at an optimum exposure dose of 5000 mJ using a projection exposure device (Ushio Inc.'s "UFX-2240"). After exposure, a 1.0 mass % aqueous solution of tetramethylammonium hydroxide at 23° C. was sprayed as a developer onto the resin composition layer at a spray pressure of 0.1 MPa for 30 seconds to perform spray development. After spray development, the resin composition layer was exposed to light at 3 J / cm. 2 The sample was then subjected to UV irradiation at 190°C for 90 minutes in a nitrogen atmosphere to obtain a sample formed of a cured resin composition layer. The refractive index (1310 nm) of the obtained sample was measured at room temperature and normal pressure using a 1310 nm laser beam with a 2010M prism coupler (manufactured by Metricon).

[0223] <Measurement of shrinkage rate> The protective film was peeled off from the resin sheet having a 10 μm-thick resin composition layer. The resin sheet was placed on a 6-inch silicon wafer so that the resin composition layer and the silicon wafer were in contact with each other, and laminated using a vacuum laminator ("VP160" manufactured by Nikko Materials Co., Ltd.). The lamination conditions were a vacuum drawing time of 30 seconds, a pressure bonding temperature of 60°C, a pressure bonding pressure of 0.3 MPa, and a pressure application time of 30 seconds. Thereafter, the support was peeled off to obtain a laminate having a silicon wafer and a resin composition layer.

[0224] The resin composition layer of the obtained laminate was exposed to ultraviolet light using a projection exposure device (Ushio Inc.'s "UFX-2240") with an exposure energy such that the number of gloss remaining steps of a 41-step tablet was 8 to 10. The exposure was performed using a quartz glass mask having a mask pattern capable of drawing multiple straight lines with an L / S (line / space) of 5 μm / 100 μm and a length of 5 cm. In the L / S of this quartz glass mask, the line corresponds to the width of the core layer, and the space corresponds to the distance between the core layers. After exposure, the substrate was left to stand at room temperature for 30 minutes, and then the support was peeled off. A 1% by mass aqueous solution of sodium carbonate at 30°C was used as a developer and spray-developed on the entire surface of the resin composition layer at a spray pressure of 0.2 MPa for 1 minute. After spray development, 2 J / cm 2 The silicon wafer was cleaved in a direction perpendicular to the lines of the obtained core, and the cross section at that time was observed under a microscope, and the vertical and horizontal lengths of the rectangular core were measured to calculate the area (α). Then, the wafer was placed in a clean oven, and the temperature was raised from room temperature to 190°C. After reaching 190°C, a heat treatment was performed for 69 minutes to harden the resin composition layer. After the resin composition layer was hardened, the same cross section was observed, and the vertical and horizontal lengths of the rectangular core were measured to calculate the area (β). The shrinkage rate c was calculated from the calculated α and β.

number

[0225] <Evaluation of dents after desmearing and measurement of adhesion (peel strength)> -Preparation of evaluation laminates B and C- The copper layer of a glass epoxy substrate (copper-clad laminate) having a thickness of 18 μm was roughened by treatment with a surface treatment agent (CZ8100, manufactured by MEC Co., Ltd.) containing an organic acid. Next, a resin sheet having a resin composition layer thickness of 20 μm was arranged so that the resin composition layer was in contact with the copper circuit surface, and laminated using a vacuum laminator (VP160, manufactured by Nichigo Morton Co., Ltd.) to form a laminate in which the copper-clad laminate, the resin composition layer, and the support were laminated in this order. The pressure bonding conditions were a vacuum drawing time of 30 seconds, a pressure bonding temperature of 60° C., a pressure bonding pressure of 0.4 MPa, and a pressure bonding time of 30 seconds.

[0226] The laminate was allowed to stand at room temperature for 30 minutes or more, and then 100 mJ / cm 2 was applied from above the support of the laminate. 2 After being left to stand at room temperature for 30 minutes, the support was peeled off from the laminate. A 1% by mass aqueous solution of sodium carbonate at 30°C was used as a developer for the entire surface of the resin composition layer on the laminate, and spray development was performed for 2 minutes at a spray pressure of 0.2 MPa. After the spray development, the coating was dried at 1 J / cm 2 This was used as laminate A for evaluation.

[0227] The insulating layer of the evaluation laminate A was subjected to a desmear treatment as follows to roughen the insulating layer. The substrate was immersed in a swelling solution (Atotech Japan's "Swelling Dip Securigant P", an aqueous solution of diethylene glycol monobutyl ether and sodium hydroxide) at 60°C for 2 minutes, then in an oxidizing solution (Atotech Japan's "Concentrate Compact CP", an aqueous solution of potassium permanganate at approximately 6% and sodium hydroxide at approximately 4%) at 80°C for 3 minutes, and finally in a neutralizing solution (Atotech Japan's "Reduction Solution Securigant P", an aqueous solution of sulfuric acid) at 40°C for 5 minutes, and then dried at 80°C for 15 minutes. The obtained substrate is referred to as evaluation laminate B.

[0228] The conductive layer was formed on the roughened surface of the insulating layer according to the semi-additive method. That is, the substrate (substrate B for evaluation) after the roughening treatment was immersed in an electroless plating solution containing PdCl2 at 40°C for 5 minutes, and then immersed in an electroless copper plating solution at 25°C for 20 minutes. Next, the substrate was heated at 150°C for 30 minutes for annealing treatment, and then copper sulfate electroplating was performed to form a conductive layer with a thickness of 30 μm, and annealing treatment was performed at 200°C for 60 minutes. The obtained substrate is called evaluation laminate C.

[0229] -Evaluation of dents after desmearing- The roughened surface of the insulating layer of evaluation substrate laminate B after the desmear treatment was observed with an SEM (magnification: 1000 times) and evaluated according to the following criteria. ◯: No depressions with a width of 2 μm or more and a depth of 1 μm or more were observed. ×: One or more depressions with a width of 2 μm or more and a depth of 1 μm or more are observed.

[0230] -Peel strength measurement- Measurement of peel strength of plated conductor layer The peel strength of the insulating layer and conductor layer was measured for evaluation laminate C in accordance with the Japanese Industrial Standards (JIS C6481). Specifically, a cut was made in the conductor layer of evaluation laminate C, measuring 10 mm in width and 100 mm in length, one end of the cut was peeled off and held with a gripper, and the load (kgf / cm) was measured when 35 mm was peeled off vertically at a speed of 50 mm / min at room temperature, to determine the peel strength. A tensile tester (TSE's "AC-50C-SL") was used for the measurement. The peel strength was evaluated according to the following criteria. ○: Peel strength is 0.20kgf / cm or more △: Peel strength is 0.15kgf / cm or more and less than 0.20kgf / cm ×: Peel strength is less than 0.15kgf / cm

[0231] <Example 1> (Evaluation of developability) -Sample preparation- A copper layer of a glass epoxy substrate (copper-clad laminate) having a copper layer of 18 μm in thickness was roughened with a surface treatment agent (CZ8100, manufactured by MEC Co., Ltd.) containing an organic acid to prepare a substrate. Next, a protective film was peeled off from a resin sheet having a resin composition layer of 10 μm in thickness, which was manufactured using the resin composition of Manufacturing Example 2. A resin sheet was placed on the copper-clad laminate so that the resin composition layer and the copper-clad laminate were in contact with each other, and laminated using a vacuum laminator ("VP160" manufactured by Nikko Materials Co., Ltd.). The lamination conditions were a vacuum drawing time of 30 seconds, a pressure bonding temperature of 60°C, a pressure bonding pressure of 0.3 MPa, and a pressure application time of 30 seconds. Thereafter, the support was peeled off, and ultraviolet light exposure was performed using a projection exposure device ("UFX-2240" manufactured by Ushio Inc.) with an exposure energy such that the number of gloss remaining steps of a 41-step tablet was 8 steps. After exposure, 2 J / cm 2 After that, the laminate was placed in a clean oven, heated from room temperature to 190°C, and after reaching 190°C, heated for 90 minutes in a nitrogen atmosphere to cure the resin composition layer. A lower clad layer was formed by the curing of the resin composition layer, and an intermediate laminate I including a copper-clad laminate and a lower clad layer was obtained.

[0232] Next, the protective film was peeled off from a resin sheet having a thickness of 5 μm produced using the resin composition of Production Example 1. The resin sheet was placed on the lower clad layer so that the resin composition layer of the resin sheet and the lower clad layer of the intermediate laminate I were in contact with each other, and laminated using a vacuum laminator ("VP160" manufactured by Nikko Materials Co., Ltd.) to form a resin composition layer on the lower clad layer. The lamination conditions were a vacuum drawing time of 30 seconds, a pressure bonding temperature of 60°C, a pressure bonding pressure of 0.3 MPa, and a pressure application time of 30 seconds. This resulted in a laminate having a copper-clad laminate, a lower clad layer, and a resin sheet in this order. Thereafter, the support was peeled off to expose the resin composition layer.

[0233] The resin composition layer was exposed to ultraviolet light using a projection exposure device (Ushio Inc.'s "UFX-2240") with an exposure energy such that the number of gloss remaining steps of a 41-step tablet was 8. The exposure was performed using a quartz glass mask having a first mask pattern for drawing straight lines with an L / S (line / space) of 50 μm / 50 μm and a second mask pattern for drawing straight lines with an L / S (line / space) of 5 μm / 5 μm. After exposure, the layer was left to stand at room temperature for 30 minutes, and then the support was peeled off. The entire surface of the resin composition layer was spray-developed with a 1% by mass aqueous solution of sodium carbonate at 30° C. as a developer at a spray pressure of 0.2 MPa for 1 minute. After spray development, the layer was exposed to 2 J / cm 2 By irradiating the copper-clad laminate with ultraviolet light for 1 hour and then performing a heat treatment at 190°C for 1 hour in a nitrogen atmosphere, sample A was obtained, which had, in this order, a copper-clad laminate, a lower clad layer, and a 5 μm-thick line layer (a layer formed of a cured product of the resin composition).

[0234] The protective film was peeled off from a 50 μm thick resin sheet produced using the resin composition of Production Example 1. The resin sheet was placed on the lower clad layer so that the resin composition layer of the resin sheet and the lower clad layer of the intermediate laminate I were in contact with each other, and laminated using a vacuum laminator ("VP160" manufactured by Nikko Materials Co., Ltd.) to form a resin composition layer on the lower clad layer. The lamination conditions were the same as those for laminating a 5 μm thick resin sheet onto the intermediate laminate I. As a result, a sample B was obtained that had a copper-clad laminate, a lower clad layer, and a 50 μm line layer (a layer formed of a cured product of the resin composition) in this order.

[0235] - Evaluation of developability - The obtained samples A and B were observed with a scanning electron microscope (SEM) (magnification 2000x) and the minimum fine line width (the width of the line layer with the smallest width among the line layers that were formed) was measured. The aspect ratio was calculated by dividing the thickness of the line layer by the minimum fine line width, and the developability was evaluated according to the following evaluation criteria. The line width refers to the width of the line layer. ◯: A line having a width of 5 μm at a thickness of 5 μm was formed, and a line having a width of 50 μm at a thickness of 50 μm was formed. Δ: Either a line having a line width of 5 μm at a thickness of 5 μm or a line having a line width of 50 μm at a thickness of 50 μm could not be formed. ×: A line having a line width of 5 μm at a thickness of 5 μm could not be formed, and a line having a line width of 50 μm at a thickness of 50 μm could not be formed.

[0236] (Optical transmission loss measurement) -Preparation of test board- 1. Formation of the lower cladding layer The protective film was peeled off from a resin sheet having a 10 μm-thick resin composition layer produced using the resin composition of Production Example 2. The resin sheet was placed on the copper-clad laminate so that the resin composition layer and the copper-clad laminate were in contact with each other, and laminated using a vacuum laminator ("VP160" manufactured by Nikko Materials Co., Ltd.). The lamination conditions were a vacuum time of 30 seconds, a pressure temperature of 60°C, a pressure pressure of 0.3 MPa, and a pressure time of 30 seconds. Thereafter, the support was peeled off, and ultraviolet light exposure was performed using a projection exposure device ("UFX-2240" manufactured by Ushio Inc.) with an exposure energy such that the number of gloss remaining steps of a 41-step step tablet was 8 steps. After exposure, ultraviolet light irradiation was performed at 2 J / cm2. The intermediate laminate II was placed in a clean oven, heated from room temperature to 190°C, and after reaching 190°C, a heat treatment was performed for 90 minutes under a nitrogen atmosphere to harden the resin composition layer. A lower clad layer was formed by curing the resin composition layer, and an intermediate laminate II including a copper-clad laminate and a lower clad layer was obtained.

[0237] 2. Formation of the core layer A protective film was peeled off from a resin sheet having a 5 μm-thick resin composition layer produced using the resin composition of Production Example 1. A resin sheet was placed on the surface of the lower clad layer of the intermediate laminate II so that the resin composition layer and the lower clad layer of the intermediate laminate II were in contact with each other, and laminated using a vacuum laminator ("VP160" manufactured by Nikko Materials Co., Ltd.). The lamination conditions were a vacuuming time of 30 seconds, a pressure bonding temperature of 60°C, a pressure bonding pressure of 0.3 MPa, and a pressure application time of 30 seconds. Thereafter, the support was peeled off, and ultraviolet light exposure was performed using a projection exposure device ("UFX-2240" manufactured by Ushio Inc.) with an exposure energy such that the number of gloss remaining steps of a 41-step step tablet was 8 steps. Exposure was performed using a quartz glass mask having a mask pattern capable of drawing a plurality of straight lines with a length of 5 cm and an L / S (line / space) of 5 μm / 100 μm. In the L / S of this quartz glass mask, the line corresponds to the width of the core layer, and the space corresponds to the interval between the core layers. After the exposure, the substrate was left to stand at room temperature for 30 minutes, and then the support was peeled off. The entire surface of the resin composition layer was spray-developed with a 1% by mass aqueous solution of tetramethylammonium at 23° C. as a developer at a spray pressure of 0.2 MPa for 1 minute. After the spray development, the spray pressure was 2 J / cm 2 Thereafter, the substrate was placed in a clean oven, and the temperature was increased from room temperature to 190° C. After the temperature reached 190° C., a heat treatment was carried out for 90 minutes in a nitrogen atmosphere to cure the resin composition layer.

[0238] A core layer was formed by curing the resin composition layer, and an intermediate laminate III including a copper-clad laminate, a lower clad layer, and a core layer in this order was obtained.

[0239] 3. Formation of upper cladding layer The protective film was peeled off from a resin sheet having a 20 μm-thick resin composition layer produced using the resin composition of Production Example 2. A resin sheet was placed on the core layer of the intermediate laminate III so that the resin composition layer and the core layer were in contact with each other, and laminated using a batch-type vacuum pressure laminator (Nikko Materials Co., Ltd., two-stage build-up laminator, CVP700). The lamination conditions were a vacuum time of 30 seconds, a pressure bonding temperature of 60°C, a pressure bonding pressure of 0.3 MPa, and a pressure time of 30 seconds. Thereafter, the support was peeled off, and ultraviolet light exposure was performed using a projection exposure device (Ushio Inc.'s "UFX-2240") with an exposure energy such that the number of gloss remaining steps of a 41-step tablet was 8 steps. After exposure, 2 J / cm 2 After that, the sample was placed in a clean oven, heated from room temperature to 170°C, and after reaching 170°C, heated for 60 minutes in a nitrogen atmosphere to cure the resin composition layer. An upper clad layer was formed by curing the resin composition layer, and a sample laminate having a copper-clad laminate, a lower clad layer, a core layer, and an upper clad layer in this order was obtained.

[0240] In this sample laminate, the combination of the lower cladding layer and the upper cladding layer constituted the cladding layer. Thus, an optical waveguide was obtained that included the cladding layer and the core layer in the cladding layer. In addition, in this sample laminate, the core layer had a linear pattern with a length of 5 cm corresponding to the mask pattern of the quartz glass mask, and the width (line width) and interval (space) of the core layer included in these patterns were consistent with the width (line width) and interval (space) of the mask pattern.

[0241] From the sample laminates manufactured using the resin sheets of the examples and comparative examples, the portion where the core layer was formed, that is, the core layer on which a 5 cm linear pattern was drawn and the clad layer around it, were cut out to obtain a test substrate equipped with an optical transmission path. The cutting conditions were as follows. Dicing equipment: DAD3221 (Disco) Blade: ZH14-SD4000-VI-50 Spindle speed: 30K / min Cutting speed: 5mm / sec Blade height: 0.060mm Dicing tape: T-80W (Denka, 80umt)

[0242] (Measurement of optical transmission loss of a calibration optical system) The transmission loss of an optical system was measured, which was configured by removing the test substrate and the light collecting module from the optical system for measuring the transmission loss of the test substrate described later. That is, a light source (1310 nm light source, THORLABS "LPSC-1310-FC") and a light receiver (Keysight optical power meter "N7742") were connected via an optical fiber (input fiber) on a vibration isolation table covered with a blackout curtain to obtain an optical system for calibration. The light source was made to emit light, and the intensity of the light that entered the light receiver was measured by the light receiver, to measure the loss of this optical system for calibration.

[0243] (Optical transmission loss measurement) A test substrate was placed on a vibration isolation table covered with a blackout curtain. A light collecting module (numerical aperture 0.18) was connected to one end (input end) of the optical waveguide of the test substrate, and a light source (1310 nm light source, THORLABS's "LPSC-1310-FC") was connected to the light collecting module via an optical fiber (input fiber). Another light collecting module (numerical aperture 0.18) was connected to the other end (output end) of the optical waveguide of the test substrate, and a light receiver (Keysight's optical power meter "N7742") was connected to the light collecting module via an optical fiber (output fiber). Through the above operations, an optical system was obtained in which light emitted from the light source passes through the optical fiber (input fiber), the light collecting module, the optical waveguide, the light collecting module, and the optical fiber (output fiber) in this order, and then enters the light receiver. Hereinafter, this optical system may be referred to as a sample optical system. The light source was turned on and the intensity of the light that entered the receiver was measured by the receiver to measure the loss of the sample optical system.

[0244] The loss of the optical waveguide included in the test substrate was determined by subtracting the loss of the calibration optical system from the loss of the sample optical system.

[0245] (Measurement of optical transmission loss (dB / cm) of optical waveguide before high temperature and high humidity environmental test (HAST test)) After the measurement of the loss of the optical waveguide having a core layer on which a linear pattern with a length of 5 cm was drawn was completed, the length was cut to 4 cm, and the same measurement was performed. After that, the length was cut to 3 cm, and the same measurement was performed, and the measured values ​​were calculated for each of the optical waveguides with a length of 5 cm, the optical waveguide with a length of 4 cm, and the optical waveguide with a length of 3 cm. The measurement results were then plotted on a coordinate system with the length of the optical waveguide on the horizontal axis and the loss of the optical waveguide on the vertical axis to obtain three coordinates representing the measurement results. An approximation line of these three points was calculated using the least squares method, and the slope of the approximation line was calculated as the loss per unit distance of the optical waveguide (optical transmission loss), and was evaluated according to the following evaluation criteria. ◎: Optical transmission loss is less than 0.4 dB / cm ○: Optical transmission loss is 0.4 dB / cm or more and less than 0.5 dB / cm △: Optical transmission loss value is 0.5 dB / cm or more but less than 1.0 dB / cm ×: Optical transmission loss is 1.0 dB / cm or more

[0246] (Measurement of optical transmission loss (dB / cm) of optical waveguide after high temperature and high humidity environmental test (HAST test)) A test substrate was prepared in addition to the test substrate used above, and left in an oven heated to 150°C for 1000 hours, and the same operation was performed to calculate the transmission loss value after the high-temperature, high-humidity environmental test. Furthermore, the rate of change (%) of the calculated optical transmission loss value after the high-temperature, high-humidity environmental test from the optical transmission loss value before the test was calculated, and evaluated according to the following evaluation criteria. ◎: Change rate is less than 10% ○: Change rate is 10% or more but less than 20% △: Change rate is 20% or more but less than 30% ×: Change rate is 30% or more

[0247] <Calculation of numerical aperture (NA)> The numerical aperture (NA) of an optical waveguide is a value expressed by the following formula (1). In formula (1), n core represents the refractive index of the cured product of the core resin composition, and n cladrepresents the refractive index of the cured product of the cladding resin composition.

number

[0248] <Measurement of shrinkage difference> The difference between the shrinkage percentage of the core layer resin composition and the shrinkage percentage of the cladding layer resin composition (shrinkage percentage of the cladding layer resin composition-shrinkage percentage of the core layer resin composition) was calculated, and the absolute value was calculated.

[0249] <Examples 2 to 9 and Comparative Examples 1 to 4> The developability, optical transmission loss, and optical transmission loss after a heat resistance test were measured in the same manner as in Example 1, except that the core layer and the clad layer were prepared using resin sheets produced using the resin compositions of the production examples shown in the table below.

[0250] [Table 2]

[0251] In each of the examples, it has been confirmed that even when components (F) to (G) are not contained, the results are similar to those of the above examples, although to different degrees. [Explanation of symbols]

[0252] 10 Optical waveguide 100 Core Layer 110 Second composition layer 111 Exposure section 112 Non-exposed area 200 Cladding Layers 210 First composition layer 220 Cured first composition layer (lower clad layer) 230 Third composition layer 240 Cured third composition layer (upper clad layer) 300 Base material 400 Mask 410 Translucent part 420 Shading part 500 Conductor Layers

Claims

1. A photosensitive resin composition set including a core resin composition and a clad resin composition, At least the cladding resin composition is (A) a high molecular weight component having a glass transition temperature of 65° C. or lower and a weight average molecular weight of 1,500 or more and less than 14,000; Including, The core resin composition and the clad resin composition each comprise: (B) a resin containing a carboxyl group, (C) an epoxy resin, (D) a photocurable resin, and (E) a photopolymerization initiator, The content (mass%) of component (A) in the clad resin composition is defined as A when the non-volatile components of the clad resin composition are defined as 100 mass%. clad The content (mass%) of the component (A) in the core resin composition is expressed as A when the non-volatile components of the core resin composition are expressed as 100 mass%. core Then, A clad -A core A photosensitive resin composition set, in which a ratio of 0.6 to 12 is satisfied.

2. 2. The photosensitive resin composition set according to claim 1, wherein the content of the component (A) is 0.1% by mass or more and 10% by mass or less, when the non-volatile components of the core resin composition are taken as 100% by mass.

3. 2. The photosensitive resin composition set according to claim 1, wherein the content of component (A) is 0.1% by mass or more and 10% by mass or less, based on 100% by mass of non-volatile components of the cladding resin composition.

4. The photosensitive resin composition set according to claim 1 , wherein component (B) comprises at least one of an aralkyl type resin, a naphthol aralkyl type resin, and a cardo type resin.

5. The content of component (B) when the non-volatile components of the core resin composition are taken as 100% by mass is defined as B core The content of the (C) component when the non-volatile components of the core resin composition are taken as 100% by mass is C core Then, B core / C core The photosensitive resin composition set according to claim 1 , wherein the ratio of the photosensitive resin composition to the photosensitive resin composition is 0.3 or more and 5 or less.

6. The content of component (B) when the non-volatile components of the core resin composition are taken as 100% by mass is defined as B core The content of component (D) when the non-volatile components of the core resin composition are taken as 100% by mass is represented by D core Then, B core / D core The photosensitive resin composition set according to claim 1 , wherein the ratio of the photosensitive resin composition to the photosensitive resin composition is 0.1 or more and 3 or less.

7. The content of component (B) when the non-volatile components of the clad resin composition are taken as 100% by mass is B clad The content of component (C) when the non-volatile components of the clad resin composition are taken as 100 mass % is C clad Then, B clad / C clad The photosensitive resin composition set according to claim 1 , wherein the ratio of the photosensitive resin composition to the photosensitive resin composition is 0.1 or more and 5 or less.

8. The content of component (B) when the non-volatile components of the clad resin composition are taken as 100% by mass is B clad The content of component (D) when the non-volatile components of the clad resin composition are taken as 100 mass % is defined as D clad Then, B clad / D clad The photosensitive resin composition set according to claim 1 , wherein the ratio of the photosensitive resin composition to the photosensitive resin composition is 0.1 or more and 3 or less.

9. The photosensitive resin composition set according to claim 1, which is a photosensitive resin composition set for producing an optical waveguide.

10. The photosensitive resin composition set according to claim 1, which is a photosensitive resin composition set for producing an optical waveguide capable of transmitting light having a wavelength of 1300 nm to 1320 nm.

11. The photosensitive resin composition set according to claim 1, which is a photosensitive resin composition set for producing a single-mode optical waveguide.

12. A photosensitive resin sheet set including a core resin sheet and a clad resin sheet, The core resin sheet is provided with a resin composition layer containing the core resin composition in the photosensitive resin composition set according to any one of claims 1 to 11, A photosensitive resin sheet set, comprising a clad resin sheet having a resin composition layer containing the clad resin composition in the photosensitive resin composition set according to any one of claims 1 to 11.

13. An optical waveguide having a core layer and a clad layer, The cladding layer is (A) a high molecular weight component having a glass transition temperature of 65° C. or lower and a weight average molecular weight of 1,500 or more and less than 14,000; (B) a resin containing a carboxyl group, (C) an epoxy resin, (D) a photocurable resin, and (E) a cured product of a cladding resin composition containing a photopolymerization initiator, The core layer is (B) a resin containing a carboxyl group, (C) an epoxy resin, (D) a photocurable resin, and (E) a cured product of a core resin composition containing a photopolymerization initiator, The content (mass%) of component (A) in the clad resin composition is defined as A when the non-volatile components of the clad resin composition are defined as 100 mass%. clad The content (mass%) of the component (A) in the core resin composition is expressed as A when the non-volatile components of the core resin composition are expressed as 100 mass%. core Then, A clad -A core An optical waveguide, wherein

14. An optical / electrical hybrid board comprising the optical waveguide according to claim 13.

15. forming a first composition layer containing a cladding resin composition; curing the first composition layer; forming a second composition layer containing a core resin composition on the first composition layer; a step of subjecting the second composition layer to an exposure treatment; subjecting the second composition layer to a development treatment; curing the second composition layer; forming a third composition layer containing a cladding resin composition on the second composition layer; and curing the third composition layer, in this order, At least the cladding resin composition is (A) a high molecular weight component having a glass transition temperature of 65° C. or lower and a weight average molecular weight of 1,500 or more and less than 14,000; Including, The core resin composition and the clad resin composition each comprise: (B) a resin containing a carboxyl group, (C) an epoxy resin, (D) a photocurable resin, and (E) a photopolymerization initiator, The content (mass%) of component (A) in the clad resin composition is defined as A when the non-volatile components of the clad resin composition are defined as 100 mass%. clad The content (mass%) of the component (A) in the core resin composition is expressed as A when the non-volatile components of the core resin composition are expressed as 100 mass%. core Then, A clad -A core A method for manufacturing an optical waveguide,

16. forming a first composition layer containing a cladding resin composition; curing the first composition layer; forming a second composition layer containing a core resin composition on the first composition layer; a step of subjecting the second composition layer to an exposure treatment; subjecting the second composition layer to a development treatment; curing the second composition layer; forming a third composition layer containing a cladding resin composition on the second composition layer; and curing the third composition layer in this order, At least the cladding resin composition is (A) a high molecular weight component having a glass transition temperature of 65° C. or lower and a weight average molecular weight of 1,500 or more and less than 14,000; Including, The core resin composition and the clad resin composition each comprise: (B) a resin containing a carboxyl group, (C) an epoxy resin, (D) a photocurable resin, and (E) a photopolymerization initiator, The content (mass%) of component (A) in the clad resin composition is defined as A when the non-volatile components of the clad resin composition are defined as 100 mass%. clad The content (mass%) of the component (A) in the core resin composition is expressed as A when the non-volatile components of the core resin composition are expressed as 100 mass%. core Then, A clad -A core A method for manufacturing an optical / electrical hybrid board,

Citation Information

Patent Citations

  • Window frame and apparatus for fixing it

    JP1982071978A

  • Photocurable thermosetting resin composition for forming optical waveguide, and cured product thereof and optical waveguide, and optoelectronic hybrid substrate, waveguide-type light splitter, and optical module including optical waveguide

    JP2019211540A